GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 547464169 species occurrences available in GBIF matching the query: HasCoordinate: true HasGeospatialIssue: false BasisOfRecord: Human Observation or Machine Observation or Observation or Material sample or Living Specimen or Literature Occurrence or Specimen. The dataset includes 547464169 records from 11357 constituent datasets: 2846 records from Coleoptera, NEF. 144 records from privater Garten. 160 records from Schussenaue bei Berg. 106 records from Mainufer. 162 records from Brander Wald (Stolberg). 2178 records from MODIRISK: Monitoring of Mosquito Vectors of Disease. 84057 records from TTU Mammals Collection. 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 372 records from Otter survey of Ireland 2004 & 2005. 3597 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209C sediments. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 45724 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 2522 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 475 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 132 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0011B. 396 records from RSPB - 2008 Farmland Bird Survey North East Wales - RSPB/CCW. 1 records from A new species of the genus Ectemnius Dahlbom, 1845 from Cameroon (Hymenoptera: Crabronidae). 2 records from Benthic hard-bottom communities abundance at X-Huinay in 2010. 2604 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 83 records from Eden Rivers Trust - White-clawed crayfish (Austropotamobius pallipes) distributions within four sub-catchments of the River Eden Catchment, Cumbria 2007-2008. 100 records from Royal Horticultural Society - Nezara viridula records held by the Royal Horticultural Society. 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 9064 records from HUFU - Herbarium Uberlandense. 3633 records from Bioimages. 1326 records from (Table T9) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P5-P7. 97 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 167-1017E sediments. 865 records from (Appendix C) Benthic foraminifera extinction group species in DSDP Site 80-548. 378 records from Tsetse flies of East Africa update. 212 records from Phthiraptera. 117631 records from Molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 30366 records from Oregon State University Herpetological Collection. 8727 records from British Lichen Society - BLS Rare and Threatened Lichen Records: Wales. 218 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 139 records from The Bat Conservation Trust - Woodland Survey. 119 records from Bryozoa of the British Isles. 389 records from Chironomid Specimen records in the Chironomid DNA Barcode Database. 10512 records from (Table T2) Plankontic foraminifera stratigraphy of ODP Hole 184-1146A. 48828 records from Grey seal at-sea distribution 2009-2014. 1252 records from Aquatic Coleoptera Conservation Trust - SNH site condition monitoring of SSSIs for water beetles 2010. 338 records from (Tab. 9.C) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 10930 records from Hymenoptera de la Colección Entomológica del Instituto Alexander von Humboldt. 53606 records from BioMar - LIFE project. 991 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 36431 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 670 records from (Table 1) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Hole 133-815A. 46664 records from The Scottish Ornithologists' Club - Fife non-breeding bird 5km atlas 1991-99. 13 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 1432 records from Naturalis Biodiversity Center (NL) - Crustacea. 129 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 336 records from Especies de Anacroneuria (Insecta: Plecoptera: Perlidae) de Colombia, depositadas en el Museo de Entomología de la Universidad del Valle (Cali, Colombia). 993 records from Rossendale Ornithologists' Club - ROC RSPB Farmland Species Survey Dataset. 57210 records from National Biodiversity Data Bank. Observation records, 1900-2014. 27932 records from Argyll Bird Club - Bird records for Argyll for the years 2002 and 2003. 333 records from Macroarthropods, Isua 2013, Greenland. 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 6 records from Peckoltia sabaji, a new species from the Guyana Shield (Siluriformes: Loricariidae).. 206 records from The Diptera Site. 24453 records from Plan de vertebrados de la Patagonia. 459992 records from Royal Dutch Angling Association (SVN) - Piscaria. 2184 records from JOI - Herbário Joinvillea. 108 records from (Table 3) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-844B. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 201 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-7. 57 records from The Game & Wildlife Conservation Trust - Capercaillie sightings Speyside 2011. 1311 records from (Table 3A) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572 and 85-572A. 1957 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD unverified freshwater fish data up to current day. 1484 records from IWDG Constant Effort Cetacean Sighting Scheme. 1904 records from Terrestrial Heteroptera Recording Scheme (Shieldbugs & allied species) - Flickr (01) Shieldbugs & allied species. 118 records from A Tenebrionid beetle’s dataset (Coleoptera, Tenebrionidae) from Peninsula Valdés (Chubut, Argentina). 2 records from Oribatids from Switzerland I. (Acari: Oribatida). (Acarologica Genavensia LXXXI). 30 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto1-10. 73514 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 2 records from (Table 10) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-854B. 273 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0012A. 1352 records from (Figure 9) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-536. 10030 records from Free-living marine Nematodes from San Julián bay (Santa Cruz, Argentine), 2009.. 172165 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine) data for Great Britain and Ireland. 385 records from (Appendix E) Size measurements of Selenopemphix undulata sp. nov. in ODP Site 202-1233. 457 records from Royal Horticultural Society - European Pear Rust (Gymnosporangium sabinae) monitoring. 1604 records from University of Calgary Herbarium. 8 records from Siphonaptera. 8169304 records from OEH Atlas of NSW Wildlife. 6885 records from ISE - Herbário ISE. 93 records from USGS SESC - Virgin Islands - Herpetofauna - 2001-2002. 4 records from Taxonomy of Afrotropical and West Palaearctic ants of the ponerine genus Hypoponera Santschi (Hymenoptera: Formicidae).. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 130 records from (Table S1) Pb/U zircon ages of ODP Hole 118-735B. 50348 records from Inventaire National du Patrimoine Naturel : Insectes Orthoptères de France. 7478 records from Merseyside BioBank - North Merseyside Reptiles and Amphibians (unverified). 168427 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 10 records from (Table C) Fauna associated with Bathymodiolus azoricus mussel beds within the Rainbow hydrothermal field, Mid-Atlantic Ridge. 231 records from (Appendix A) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 107-654A. 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 190 records from Herpetofauna laguna El Tinije. 31884 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 7008 records from HUEM - Herbário da Universidade Estadual de Maringá. 477 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Leie in Flanders, Belgium. 277 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 1 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 8 records from Dendrogramma, New Genus, with Two New Non- Bilaterian Species from the Marine Bathyal of Southeastern Australia (Animalia, Metazoa incertae sedis) – with Similarities to Some Medusoids from the. 401 records from (Fig. 7) Coccolith species abundance of sediment core GeoB11035-1. 1152 records from (Table 12) Benthic foraminifera in Eocene-Oligocene sediments of DSDP Hole 90-592. 74 records from (Table 3) Abundance of benthic foraminifera and ostracoda in bottom sediments from the Ashadze-1 Hydrothermal Field. 58 records from (Table 4a) Range chart of benthic and planktonic foraminifera of ODP Hole 127-796A. 66 records from (Table T8) Calcareous nannofossil stratigraphy of ODP Hole 198-1211A. 19 records from Revision von Suctobelba trigona (Michael, 1888). 279 records from Dieta del Piquero Café (Sula leucogaster etesiaca) en el Parque Nacional Natural Gorgona, Pacífico colombiano.. 1 records from Pollen analysis of sediment profile KAIX_B from Kaiserwinkel. 55785 records from PRECIS (KwaZulu-Natal Herbarium). 56170 records from University of Vienna, Institute for Botany - Herbarium WU. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 10552 records from Biological Records Centre - Collembola Recording Scheme. 4789 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 1144 records from Colección de Entomología - Diptera - Ceratopogonidae. 586 records from RSPB - Farmland bird database in Dumfries and Galloway, 1999-2010 (RSPB). 909 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 164 records from EcoRecord - Reptile records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 9543 records from RSPB - Wader survey on Uist in 2007 (RSPB/BTO). 1 records from ISM Mammalogy Collection. 1741 records from EcoRecord - Mollusc records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 8927366 records from Botanical Society of the British Isles - Vascular Plants Database. 1235 records from Insect Collection (CeStuBio). 160 records from Scottish Natural Heritage - Distribution of Scottish wildcats (Felis silvestris) in Scotland (2006-2008) â database extract (breeding and non-breeding records). 380 records from USGS SESC - Biscayne - Herpetofauna - 2002-2003. 1334 records from (Table 5) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-848B. 29470 records from Phanerogamic Botanical Collections (S). 5834 records from National Lesser Horseshoe Bat Database. 7034 records from Mollusca collection of National Museum of Nature and Science. 85 records from Studies on species of Holarctic Pardosa groups (Araneae, Lycosidae). VII. The Pardosa tesquorum group. 77 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 246869 records from MVZ Herp Collection (Arctos). 642 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 5729 records from Alterra (NL) - Entomofauna inventory in cattle grazed dune grassland. 5709 records from Coleoptera of Piska Forest. 355 records from Herbier G. Garapin (BOUM). 4107 records from Anthomyiidae Study Group - Anthomyiidae records for Great Britain. 6992 records from RSPB - Stone-curlew Annual Surveys (RSPB/Natural England). 2418 records from (Figure 9) Distribution of Maaestrichtian planktonic foraminifera in ODP Hole 132-810C. 1997 records from Aves de la cuenca media del río Bogotá. 3806 records from USGS SESC - Everglades - Herpetofauna - 2005. 26385 records from The Environmental Sample Collection of the Arthropoda Varia Section at the Zoologische Staatssammlung München. 20 records from Truchas Mexicanas. 3 records from MSB Mammal Observations (Arctos). 69751 records from African Rodentia. 111151 records from Jordal. 28924 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 1988 records from (Appendix 2) Benthic foraminifera in ODP Hole 160-963A. 244 records from Scottish Natural Heritage - The ecology of Najas flexilis (Slender naiad). 8 records from A review of the ant genus Metapone Forel from Madagascar.. 35 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2001. 9302 records from Ants from the Paraguayan dry Chaco. 2141 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 38541 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD other mammal data up to current day. 38567 records from Marine species distributions in Irish coastal waters. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 353 records from Coastal and marine species. 980 records from (Table AT7) Planktonic foraminiferal stratigraphy of ODP Hole 182-1132B. 140022 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 6800 records from Tromsø Museum, Bryophytes. 941 records from (Appendix 1) Benthic foraminifera in eastern equatorial Indian Ocean surface sediments. 23 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 4611 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Aves. 2 records from Scottish Natural Heritage - Survey of White-clawed crayfish Austropotamobius pallipes in Scotland. 58938 records from Biological Records Centre - Isopoda (Interim dataset). 5824 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Yser in Flanders, Belgium. 1 records from (Table 4) Thecosomata in ODP Hole 134-831A. 4 records from A new species of Simopelta (Hymenoptera: Formicidae: Ponerinae) from Brazil and Costa Rica. 202 records from Biodiversity Information Service for Powys and Brecon Beacons National Park - Distribution of Impatiens glandulifera Royle along the river Irfon during June 2010. 1808 records from University of Amsterdam (NL) - Páramo vegetation research, Ecuador.. 42 records from (Table 2) Benthic foraminifers at DSDP Hole 72-515A. 89874 records from ecoscope_observation_database. 232 records from (Table A1) Stratigraphic distribution of calcareous nannofossils of ODP Hole 198-1210A. 74 records from (Table T5) Cretaceous calcareous nannofossil abundance of ODP Hole 173-1069A. 5 records from Order Diptera, family Mydidae. 2 records from Pollen analysis of sediment profile AUL00 from Steeger See. 1172 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1215A sediments. 457499 records from Bird Atlas 2007 - 2011. 1603 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 554 records from Portuguese Seaweeds. 41 records from (Table T5) Calcareous nannofossil abundance of ODP Hole 189-1172A sediments. 304 records from John Muir Trust - Bryophytes of Glen Nevis Woods 1987-1988. 1230771 records from AntWeb. 85 records from Biotop "Kohlbeke" (Berlin-Marzahn). 3681 records from UFG - Herbário da Universidade Federal de Goiás. 1702 records from BioGIS - Bryophytes - HUJ collections. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 212 records from Colección nacional de palmas de Colombia - JBQ. 1710 records from (Table 8E) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 19-4 through 25-5. 4198 records from Planktic foraminifera (%) of sediment core MD96-2085. 5248 records from (Figure 2) Range and distribution chart of dinoflagellate cysts recovered from Campanian to Maestrichtian sediments at DSDP Hole 95-612. 10 records from Inventarios de Murciélagos Pauto M, La Primavera, Yopal, Casanare. 1025 records from (Appendix 2) Absolute abundance of nannofossils in ODP Hole 183-1135A. 2546 records from The atlas of butterflies in Kraków. 165 records from Palaeoclimate records over the past 22,000 years of sediment core GeoB10053-7. 70222 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 114137 records from Australian National Wildlife Collection provider for OZCAM. 2595 records from Faunal Inventory of Morysin Nature Reserve. 64 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 4251 records from Aves de la cuenca media del río Chambery, Caldas. 288 records from Fungi of Słowiński National Park, Poland. 4316 records from PolE At Sea Observations of Birds and Marine Mammals during PS 81 (ANT-XXIX/4). 304 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar2. 561 records from Herpetile collection, Natural History Museum, University of Oslo. 211338 records from MVZ Mammal Collection (Arctos). 6239 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 15181 records from British Lichen Society - BLS Lichen Database: Welsh churchyards. 896 records from Trichoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 215 records from (Table 8) Benthic foraminifera genera assemblage at DSDP Section 80-548A-28. 1015 records from Irish Marine Turtle Database. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 511 records from Coleoptera of Swierklaniec Forest. 2407 records from GRBGT: Southern Cape Herbarium Specimen Collections (1882-2008). 60131 records from QLD DERM Coastal Bird Atlas (Trial). 163 records from (Table 4) Benthic foraminifera genera assemblage at DSDP Section 80-548A-11-3. 546876 records from Bee Biology and Systematics Laboratory. 4730 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 3042 records from dec2011. 11945 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 13566 records from Highland Biological Recording Group - HBRG Fungus, Lichen and Lower Plants Dataset. 214 records from Collection of Heteroptera. 5581 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-994C. 2 records from First record of the genus Leptanilloides (Hymenoptera: Formicidae: Dorylinae) from the United States. 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 25002 records from Bryophyta collection of the Botanical Museum of the University of Oulu. 113964 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 179917 records from LACM Entomology Collection. 33 records from New records in vascular plants alien to Kyrgyzstan. 506471 records from Consortium of California Herbaria. 9874 records from Orthopteroidea. 37968 records from Online Atlas of vascular plants 2012-2020. 1616 records from Gloucestershire Centre for Environmental Records - Gloucestershire Reptiles. 2480 records from Woodland Condition Survey Group - Plants recorded during the non-SSSI woodland condition survey 2011. 23048 records from RSPB - Swift Inventory of Low-Level Screaming Parties in the UK, 2009 (RSPB and Swift Conservation Groups). 8302 records from Joint Nature Conservation Committee - Scotland Otter Survey Database. 47570 records from Naturalis National Natural History Museum (NL) – Insecta_Lepidoptera_SE Asia and other regions. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 5864 records from Herbarium Vonderau - FULD. 527 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 8784 records from Censo de aves acuáticas invernantes de la Comunidad Autónoma del País Vasco. 476 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 145 records from (Tab. 9.B) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 768 records from (Table 3) Benthic foraminifera in Southwest Indian Ocean surface sediments. 295987 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 19 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 1 records from Red list project inventory, bryophytes. 328 records from Insect Collection from New Caledonia. 85 records from Insektenvielfalt Ahe/Weichelsee. 8367 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 1211 records from CCBER Herpetology Collection. 204 records from (Table 8) Sample mass, sand fraction and relative abundances of planktonic foraminifera in ODP Holes 127-794A and 127-197B. 45112 records from IAC - Herbário do Instituto Agronômico de Campinas. 51297 records from Scottish Wildlife Trust - The Scottish Squirrel Database. 6 records from (Table 1) Abundance of ciliates, dinoflagellates, nauplii and krill at different stations in the Godthabsfjord. 854 records from Flora vascular de las llanuras aluviales del bajo río Nechí. 6660 records from Weevils of the Tatra Mts.. 20 records from Marine gastropods and other remains profile from sediment core AV14_K2-3. 7250 records from All Ireland Marsh Fritillary Database. 5733 records from Small Mammal Research Database. 3754 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Types. 352 records from Scottish Natural Heritage - Recovery of the medicinal leech Hirudo medicinalis in Scotland - Phase II. 182 records from (Table VII) Benthic foraminifera abundance in the Great Belt Channel. 1206 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1172A sediments. 96 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 116 records from Concentration of organic-walled dinoflagellate cysts from 116 marine surface samples. 1 records from Lissotes working-group. 2253 records from Biological Records Centre - Muscidae (Diptera) records from Britain and Ireland to 1985. 876791 records from Naturalis Biodiversity Center (NL) - Botany. 423 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 100 records from Brock University Herbarium (BU). 230 records from Herbarium Senckenbergianum (GLM) - Lichenes. 36413 records from RSPB - Corncrake national surveys - raw data (SCARABBS). 1134 records from PReCAST Marine Mammal Sightings. 2484 records from Marine Environmental Monitoring - Marine Turtles. 25530 records from (Table 1) Distribution of planktonic foraminifera in ODP Site 130-806. 9082 records from Inventaire National du Patrimoine Naturel : Crustacés Décapodes de France. 1200 records from monocotyledonous_geophytes_of_fergana_valley. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 562077 records from Fishbase. 185 records from Macrozoobenthos abundance of the intertidal zone of a sandy beach at the Island Algodoal-Maiandeua, Pará, Brazil. 4965 records from SANT herbarium vascular plants collection. 9376 records from RSPB - White-tailed eagle reintroduction in Scotland - Sightings data (RSPB/SNH). 670 records from Diptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 176654 records from CAS Entomology (ENT). 336 records from (Table T3) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P5-P6b. 224 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 8 records from Six new species of ants (Insecta: Hymenoptera: Formicidae) from Egypt.. 2130 records from Zoology (Museum of Evolution - Uppsala). 22451 records from Biodiversity Research and Teaching Collections - TCWC Marine Invertebrates. 548 records from (Tab. 9.D) Presence and abundance of benthic fauna at station FINO 1 in 2005. 67 records from A taxonomic revision of the catshark genus Haploblepharus Garman 1913 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 16774 records from KUBI Ornithology Tissue Collection. 10898 records from SPSF - Herbário Dom Bento José Pickel. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 10135 records from Royal Horticultural Society - RHS lily beetle (Lilioceris lilii) monitoring. 24377 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 234 records from (Table T4) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1211B, Shatsky Rise, Pacific Ocean. 55 records from (Table S2a) Nannofossil species richness in the Bass River section. 891282 records from PRECIS. 8581 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, archived data (2001-2008) - sensitive records. 49 records from (Table 8) Pliocene to Pleistocene nannofossil range chart for ODP Hole 134-833B. 28172 records from Notes from the Mycology Herbarium, Oslo (O). 2 records from A distinctive new species of gnatcatcher in the Polioptila guianensis complex (Aves, Polioptilidae) from western Amazonian Brazil. 1 records from The larva and prepupa of Eupareophora exarmata (Thomson, 1871) (Hymenoptera, Tenthredinidae). 670341 records from PlutoF platform observations. 28 records from (Table 2) Oligocene to Pliocene nannofossil range chart for ODP Hole 134-828A. 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 225 records from (Table T2) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 6198 records from Plecoptera. 1091 records from Colección de Crustacea del Museo Nacional de Historia Natural de Chile. 188 records from Inventaire National du Patrimoine Naturel : Observations d'hippocampes et syngnathes de France métropolitaine: Programme Hippo-ATLAS. 4738 records from (Table 3) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-845A. 23037 records from CSIRO Ichthyology provider for OZCAM. 59522 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 211 records from Irish Federation of Sea Anglers Catch Data. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 91719 records from Dutch Centre For Field Ornithology (SOVON) - Breeding Bird Monitoring Program. 64 records from (Table 2) Planktonic foraminifera species found in sediment trap samples and bottom sediments at Station Vy20-3178. 3 records from Fossil occurrence of calcareous nannofossils from IODP Hole 319-C0009A. 3083 records from Finnish Entomological Database: Heteroptera. 47 records from New data on the jumping spiders of the subfamily Spartaeinae (Araneae: Salticidae) from Africa. 1427 records from Colección de aves del Museo de Historia Natural de la Pontificia Universidad Javeriana. 3884 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 6425 records from Likona Invertebrates. 24 records from (Table 1) Stage of the lemming cycle and nesting parameters of the greater snow geese between 1996-2005, Bylot Island. 28772 records from EPA River Biologists data. 190 records from Relative abundance of ostracods in sediment core Sv09. 216 records from (Table A2) Stratigraphic distribution of major planktic foraminifer species of ODP Hole 198-1210A. 101412 records from Occurrence records of southern African aquatic biodiversity. 7265 records from NHM, Heteroptera. 715 records from Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 5 records from (Figure 8) Relative abundance of nannoliths at DSDP Hole 62-464. 262155 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 2 records from Collection Myriapoda - SNSD. 9349 records from Harriet Irving Botanical Gardens (HIBG). 930 records from RSPB - Black-throated diver national surveys in Scotland (SCARABBS). 2322 records from (Table AT8) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134A. 12 records from New records of Trichoceridae (Diptera) from the island of Mallorca ​. 367 records from Clyde River Foundation - Twaite Shad (Alosa fallax) distribution for Scotland, historical to present. 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 7 records from Benthic hard-bottom communities abundance at X-Huinay in 2012. 353 records from Colección de Entomología - Arthropoda. 2498 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1168A sediments. 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 2336 records from Glasgow Museums BRC - Mammal records for Clyde Faunal Area, 1850 to 2007. 559 records from (Table 2) Planktonic foraminifera community at DSDP Hole 94-610. 31 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto39-47. 163199 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 17618 records from BioGIS - Mammals - INPA database. 21698 records from SPF - Herbário da Universidade de São Paulo. 2560 records from (Table T2) Planktonic foraminifera stratigraphy of ODP Hole 198-1211C sediments. 3176 records from Colección de Ornitología - Museo de Ciencias Naturales de La Salle. 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 13 records from Perot Museum of Nature and Science. 346 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 8 records from Three new species of seasonal killifishes of the Simpsonichthys antenori species group (Teleostei: Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, Brazil.. 23 records from (Table 2) Live (stained) benthic foraminifera from stations in the northern Gulf of California. 2 records from Kryptopterus platypogon, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 10306 records from Cercle des mycologues de Montréal Fungarium (CMMF). 1 records from Zooplankton abundance measured on water bottle samples during Jan Mayen cruise JM7. 55 records from Von A(horn) bis Z(ecke) des WWP Chemnitz. 9 records from (Appendix B) Relative abundance of benthic foraminifera morphotypes in ODP Hole 138-844C. 829 records from Devon Biodiversity Records Centre - Dartmoor National Park survey data (1910-1970). 965 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 139243 records from SLU Aqua Institute of Coastal Research Database for Coastal Fish - KUL. 32 records from (Table T1) Dinoflagellate cyst and spore/pollen yield and preservation in ODP Leg 188 sites. 384 records from (Supplement Table) Individual body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 163 records from (Table 11) Relative frequencies of planktonic foraminifers and cluster arrangement of ODP Holes 127-794A and 127-197B. 174497 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 164937 records from KUBI Mammalogy Collection. 15 records from Projeto Abrace o Boto Cinza. 4432 records from Lepidoptera (Observations). 18521 records from Species plots from the Norwegian Vegetation Mapping Programme. 12808 records from WIWO (NL) - Migration of Pacific Golden Plovers through North-Eastern Mongolia. 1354 records from (Table 1) Planktonic foraminiferal communities at DSDP Holes 94-609B and 94-609. 15817 records from UFP - Herbário UFP - Geraldo Mariz. 55 records from (Table 3) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840B. 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 47 records from Empria and Monsoma in Japan. 39 records from Südpark (Bochum-Wattenscheid). 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 76858 records from Conchological Society of Great Britain & Ireland - Mollusc (marine) data for Great Britain and Ireland. 4 records from Six new, unusually small ants of the genus Leptomyrmex (Hymenoptera: Formicidae).. 1 records from Revision der Ceratozetidae, 5. Ceratozetes thienemanni WILLMANN (Arach., Acari, Oribatei). 1432 records from University of Amsterdam (NL) - Páramo pollen reference collection. 61 records from Registros restauración ecológica- Magdalena medio. 11518 records from Merseyside BioBank - North Merseyside Insects (verified). 1490 records from (Appendix) Benthic foraminifera in early Eocene sediments of DSDP Hole 48-401. 105 records from People's Trust for Endangered Species - Noble Chafer: Pre-BAP records prior to 1998. 1847244 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 14 records from Inventario Herpetológico Pauto J, Rincón del Soldado, Yopal, Casanare. 412 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001E. 6163 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 28 records from RSPB - Black grouse lek survey in Moray and Nairn 2009 (RSPB). 1 records from Herpetology. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 10 records from Pauropoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3560401 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 26847 records from Merseyside BioBank - North Merseyside Other Taxa (unverified). 63 records from (Data S1) Palynology of ODP Site 119-739. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 140 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 5 records from Oribatid mites from Switzerland, IV (Acari: Oribatida: Suctobelbidae). 654 records from Helgeland Museum, Tabanidae. 592367 records from Waarnemingen.be - Butterfly occurrences in Flanders and the Brussels Capital Region, Belgium. 124 records from (Appendix A1) Cenomanian benthic foraminifera of ODP Hole 207-1258A. 218 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 2. 618 records from RSPB - Scottish Crossbill National Survey in the UK in 2008 (SCARABBS). 19122 records from Biological Records Centre - Cerambycidae Dataset. 5079 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 23366 records from Herbario Pontificia Universidad Javeriana. 12 records from (Table 1) Length, weight, fat content and age of Norwegian spring spawning herring (Clupea harengus) during 2007. 93 records from (Table 5) Oligocene to Pleistocene nannofossil range chart for ODP Hole 134-829A. 36972 records from Environment Agency - Environment Agency Rare and Protected Species records v1. 2 records from A third species in the rare Australian ant genus Peronomyrmex Viehmeyer (Hymenoptera: Formicidae).. 71617 records from The avian collection at the Natural History Museum, Oslo, Norway. 322 records from Triebesbach (Zeulenroda-Triebes). 35762 records from Colección Herbario Federico Medem Bogotá - FMB. 2608 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 2011 records from Local BioBlitz Challenge 2013. 883082 records from FLORIVON. 111581 records from Highland Biological Recording Group - HBRG Insects Dataset. 94709 records from Merseyside BioBank - North Merseyside Flowering Plants (unverified). 386572 records from Species data extracted from the National Vegetation Database. 381 records from Iberian Peninsula and Balearic Island Bathynellacea (Crustacea, Syncarida) database. 213 records from A taxonomic review of the genus Azteca (Hymenoptera: Formicidae) in Costa Rica and a global revision of the aurita group.. 1159 records from API_CRSN_Data. 1 records from Adetomyrma, an enigmatic new ant genus from Madagascar (Hymenoptera: Formicidae), and its implications for ant phylogeny.. 19 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 4025 records from Colección Herpetológica del Museo Nacional de Historia Natural de Chile. 22639 records from IICT Herbário LISC. 358 records from (Appendix D) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Site 161-975. 7436 records from URM - Herbário Pe. Camille Torrand. 751 records from Trichoptera (caddisflies) of Ireland. 601 records from Dinoflagellate cyst species of sediment core GeoB10732-3. 807 records from National Trust for Scotland - NTS Properties Sensitive Species Records 1800-2013. 103104 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 528 records from Collection Crustacea - KAUMM. 44 records from Solanum_baretiae. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 105 records from Schulgarten Hans-Carossa-Oberschule. 68 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 2089 records from Crustáceos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CERBMcr-UV). 6139 records from HERBAM - Herbário da Amazônia Meridional. 2107 records from MLZ Mammal Collection (Arctos). 20390 records from ICN - Herbário do Instituto de Ciências Naturais. 28362 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 225 records from Meiobenthos of target sites of Crimea in 2009/2010. 1093 records from Abundance of megabenthic species in trawl catches per station in addition to table 2 during POLARSTERN cruise ARK-VIII/2 (EPOS). 43881 records from University of Alberta Vascular Plant Herbarium (ALTA). 3 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 338 records from Longhorn and buprestid beetles (Coleoptera: Cerambycidae, Buprestidae) of the forest-steppe “Bielinek” reserve and its surroundings. 73 records from (Table 7) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-850B. 1197 records from North Atlantic (Rockall Plateau) coccolith assemblage data for MIS 5 of ODP Hole 162-980B. 52 records from A taxonomic revision of the catshark genus Poroderma Smith, 1837 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 4369 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 4944 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 2 records from On the female of Gypona reversa DeLong & Martinson, 1972, with emphasis on genital structures (Insecta: Hemiptera: Cicadellidae). 16826 records from Tachinid Recording Scheme - Tachinid Recording Scheme - GB and Ireland records. 20 records from (Table 2) Counts of live (stained) benthic foraminifera from stations in the northern Gulf of California. 81747 records from Herbario Universidad de Antioquia (HUA). 6 records from (Table 3) Middle Eocene silicoflagellates from DSDP Hole 95-613. 24 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2003. 3257 records from fundiv france database. 500 records from Colección de Reptiles del Instituto Alexander von Humboldt. 76 records from (Fig. 2) Vertical density profiles of meiofauna taxa in surface sediments of Potter Cove, King George Island, Antarctic Peninsula. 5053399 records from Southern African Bird Atlas Project. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 7403 records from Freshwater fishes of Hidalgo state (Mexico) in the MZNA fish collection of the University of Navarra (Spain). 552 records from (Table 2) Relaticve abundances of Eocene to Oligocene planktonic foraminifera in ODP Hole 135-841B. 456 records from Levantamento de Arbóreas do Parque Nacional do Jaú. 129435 records from Inventaire National du Patrimoine Naturel : Mammifères de France. 745 records from (Table 2) Benthic foraminifers at DSDP Hole 72-518. 61980 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 60710 records from Leicestershire and Rutland Environmental Records Centre - Leicestershire & Rutland Coleoptera. 615 records from Colección de Aves Museo Universitario de la Universidad de Antioquia. 231866 records from Lyman Entomological Museum (LEMQ). 39 records from University Marine Biological Station Millport - 1995 EC Study Contract Clyde Sea Nephrops Stock Assessment Study. 7873 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Himalayan Balsam Surveys (WT) - 2010-2012. 52 records from Isotope tracer experiment: meiofauna counts. 96 records from (Table T4) Biogenic and mineral composition of sediments cored in Hamburg-Langenhorn. 4853 records from University of Alberta Museums, Entomology Collection. 2 records from Bridging the distributional gap of Tylorida striata (Thorell, 1877) and new synonymy (Araneae: Tetragnathidae). 18 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001I. 991 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 194 records from Colección Herpetológica de la Patagonia. 61002 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 1423 records from Reptilia notes, NTNU, Trondheim. 34502 records from Merseyside BioBank - North Merseyside Birds (verified). 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 86071 records from NINA Vanndata øvrige arter. 175 records from (Table 6) Benthic foraminifera genera assemblage at DSDP Section 80-548A-16-3. 721 records from Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 100 records from The South American annual killifish genus Austrolebias (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology and taxonomic revision.. 69595 records from Lepidoptera collection, Natural History Museum, University of Oslo. 50453 records from VIS - Fishes in estuarine waters in Flanders, Belgium. 945 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 202 records from BTCV Scotland - BTCV wildlife counts recording workshops. 9037 records from The Scottish Ornithologists' Club - Highland bird data 2002 - 2003 - non-breeding records. 106 records from (Appendix II) Foraminifera abundance in DSDP Hole 22-214. 4 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2012. 9757 records from Collection of Coleoptera. 1722 records from Cambridgeshire & Peterborough Biological Records Centre - Orthoptera dataset held by CPERC. 611 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 364 records from published_chenopodium_vulvaria_observations. 534 records from Ascomycetes of Russian Fennoscandia. 26152 records from Herts Bird Club - Hertfordshire Breeding Bird Atlas : 1967-1973. 5 records from A revision of the western hemisphere Chalcoscirtus (Araneae: Salticidae). 8871 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 1627 records from RSPB - Bird survey records from RSPB's London House Sparrow Parks Project 2009-2010, covering 19 London parks and surrounding streets (Funded by SITA Trust,. 10 records from Devon Biodiversity Records Centre - Devon giant hogweed data 1997 to 2000. 2782 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Taminango, Nariño. 34 records from Aschelminth collection of National Museum of Nature and Science. 327 records from (Table 1) Fossil record of foraminifera and ostracoda from Albersdorf clay pit, north Germany. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 1 records from A New Species from Mountain Forest Soils in Japan: Porosia paracarinata sp. nov., and Taxonomic Concept of the Genus Porosia Jung, 1942. 9 records from Inventario Herpetológico Pauto M, La Primavera, Yopal, Casanare. 17782 records from The Bat Conservation Trust - Colony Count Survey. 1349 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 30 records from Studies on the Zoarcidae of the southern hemisphere. X. New records from western Antarctica.. 91 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 1591873 records from SA Flora (BDBSA). 19741 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 455 records from (Table T2) Calcareous nannofossil abundance across the Oligocene/Miocene boundary of ODP Hole 189-1168A sediments. 31 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1998. 55897 records from AM: Freshwater Invertebrates (1900-2005). 3 records from Myoglanis aspredinoides (Siluriformes: Heptapteridae), a new catfish from the Río Ventuari, Venezuela.. 12244 records from ULg_Hexapoda. 2295 records from Joint Nature Conservation Committee - England Otter Survey Database. 5368 records from Dutch Mammal Society (NL) - Mammal observations extracted from historic reports. 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 8398 records from UAM Fish Collection (Arctos). 364 records from The Fish Collection at the Zoologische Staatssammlung München. 464 records from Colección de Crustáceos Decápodos y Estomatópodos del Centro Oceanográfico de Cádiz: CCDE-IEOCD. 1 records from Schizomida Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 57 records from verschiedene Kleingewässer um Oldenburg/Holstein. 1371 records from (Table T2) Abundance of dinoflagellates and other palynomorphs in Eocene-Oligocene sediments from ODP Hole 189-1172A. 1 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 71 records from RSPB - Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010.. 11 records from Pollen profile from sediment core AV14_K2-4. 46 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 880 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 1364 records from Irish Collembola records. 11826 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Netherlands. 97 records from RSPB - Twite national sample survey in the UK in 1999 (SCARABBS). 2448 records from (Table T2) Abundance of stratigraphically important planktonic foraminifera in ODP Hole 186-1151A sediments. 393 records from Danish Lacewings (Neuroptera). 1998 records from CESJ - Herbário Leopoldo Krieger. 583 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-847B. 1 records from Five new species of the damselfish genus Chromis (Perciformes: Labroidei: Pomacentridae) from deep coral reefs in the tropical western Pacific.. 342 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 146 records from Megophthalmidia_of_North_America. 8326 records from Derbyshire Biological Records Centre - Derbyshire Invasive Vascular Plants (INNS) 1900 - 2011. 11 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 78981 records from NCSM Fishes Collection. 9127 records from Colección de líquenes del Herbario "Jaime Andrés Rodríguez". LEB-Lichen. 360 records from (Figure 1g) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3174. 200 records from (Table T1) Neogene stratigraphy of diatoms, ebridians and endoskeletal dinoflagellates in ODP Hole 183-1138A. 1323 records from (Table 10) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-591. 841 records from Dorset Environmental Records Centre - Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 5872 records from EcoRecord - Beetle (Coleoptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 22937 records from Amphibian Specimens. 27 records from RSPB - Bearded Tit National Survey in Britain 1992 (SCARABBS). 2802 records from Merseyside BioBank - North Merseyside Fish (unverified). 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 184 records from Scorpiones collection (RS) of the Muséum national d'Histoire naturelle (MNHN - Paris). 216 records from (Table T1) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1135A. 782 records from Lowland lakeshore vegetation in Nord-Trøndelag, Norway. 19237 records from Alterra (NL) - Biological Indicator Soil Quality-Microarthropods inventory in different habitats. 34 records from Sipuncula collection of National Museum of Nature and Science. 6083 records from Biological Records Centre - Sepsidae (Diptera) records from Britain and Ireland to 1985. 31 records from RSPB - Spotted crake national survey in the UK in 1999 (SCARABBS). 19 records from (Table 1) Abundance of unicellular eukaryotes in ice cores collected during the July 2008 CCGS Amundsen cruise in Darnley Bay. 1625 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 355 records from Culture Collection of Cryophilic Algae. 767 records from BioGIS - Bats - Asaf Tsoar database. 6 records from On a new species of the genus Moenkhausia Eigenmann (Ostariophysi: Characidae).. 373 records from Dinocyst occurrences and zonations from IODP Hole 313-M0029A. 733 records from Antarctic Porifera database from the Spanish benthic expeditions: Bentart, Gebrap and Ciemar. 3688 records from Clare Biological Records Centre dataset. 2466 records from TTRS Ornithology. 582 records from Bioblitz 2013 Copenhagen Denmark. 11 records from (Table AT2) Petrology in point counts of ODP Hole 210-1276A, two ODP Leg 173 sites and DSDP Hole 47-398D. 68110 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 139 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 236 records from GENT Lactarius Deliciosi. 201 records from BioAcoustica: Wildlife Sounds Database. 25983 records from Monitoring data from the federal state Bavaria (Germany). 567 records from Collection of Hymenoptera. 8 records from (Table 2) Monthly statistics of king penguin (Aptenodytes patagonicus) colony arrivals, Possession Island. 45 records from Sediment age, abundance of planktonic foraminifera shells, degree of their dissolution, percentage of benthic foraminifera in total foram fauna, Core GC-11, Sea of Okhotsk. 425 records from Líquens d'Andorra. 1408 records from (Table 2) Distribution of Campanian-Maestrichtian agglutinated foraminifers in DSDP Hole 78-543A. 33497 records from Dragonfly Ireland. 4202 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 337737 records from BioFokus. 45 records from Scottish Natural Heritage - Surveys of Najas flexilis (Slender naiad) in Scotland 2004 â 2011. 146932 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 31 records from Fundación Miguel Lillo - Colección Invertebrados. 2 records from Ituglanis paraguassuensis sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new catfish from the rio Paraguacu, northeastern Brazil.. 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 8 records from (Table 1) Trawled distance, Isopoda per 1000 m haul length, expected number of species, evenness, and the Shannon-Wiener index during POLARSTERN cruise ANT-XIX/3 (ANDEEP I). 1287 records from RAVON (NL) - Fish observations extracted from Hoek (1888) and Hoek (1897). 968 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones Palpha-P3b. 7203 records from Royal Horticultural Society - Records from the RHS insect reference collection. 1764 records from Aves Playeras y Otras Aves Asociadas a Arrozales en los Departamentos de Casanare y Meta en 2009 - 2010. 108 records from (Table 5) Live benthic foraminifera in sediment core SO130-236MC. 68 records from Late Pleistocene planktonic foraminifera of Hole 302-M0004C (Addendum 1). 1557 records from Hypogean Crustacea recording scheme - Hypogean macro-Crustacea records. 6 records from A new Savignia from Cretan caves (Araneae: Linyphiidae). 149 records from (Appendix A) Palynofacies raw counts of DSDP Hole 38-338. 487 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 14601 records from Vertebrats d'Andorra. 34763 records from DMNS Bird Collection (Arctos). 78799 records from natagora-earlybirds. 80907 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 1131 records from (Table T8) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zone P4. 6 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 588 records from Relative abundance of ostracods in sediment core Lz1120. 39035 records from Merseyside BioBank - North Merseyside Birds (unverified). 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 15 records from (Table 1) Occurrence and abundance of late Early Cretaceous radiolarians at DSDP Hole 62-463. 176 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2010. 33 records from Relative abundance of Florisphaera profunda in ODP Hole 121-758C. 5 records from (Table 2) Osmium isotope ratios and Re-Os element content for cleaned and uncleande foraminifera of ODP Hole 121-758A. 53 records from Royal Horticultural Society - Wisteria scale (Eulecanium excrescens) records acquired by the Royal Horticultural Society. 133180 records from NINA insect database. 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 2 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 808 records from Greater Manchester Ecology Unit - Distribution of Great Crested Newts in Greater Manchester. 5 records from Specimen records associated with "A troglomorphic spider from Java (Araneae, Ctenidae, Amauropelma). 17 records from (Table A) Fauna associated with Bathymodiolus azoricus mussel beds within the Menez Gwen hydrothermal field, Mid-Atlantic Ridge. 6330 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 43 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 546 records from OUPR - Herbário "Professor José Badini". 45 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 43 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida). 644 records from (Table T1) Planktonic foraminiferal stratigraphy of ODP Hole 173-1065A sediments. 30 records from (Table 1) Carbonate constituents and quartz in the sand-sized fraction in Mississippi Fan sediments, DSDP Hole 96-615. 873 records from Kartlegging av spredning av fremmede bartrær. 9904 records from CUMV Mammal Collection (Arctos). 719899 records from Fauna Atlas N.T.. 12 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1996. 15597 records from Countryside Council for Wales - Skomer Marine Nature Reserve (MNR) Marine Monitoring Programme. 69125 records from CAS Invertebrate Zoology (IZ). 69 records from "Schwarzes Teich" (Waldpark Radebeul). 76 records from (Appendix A2) Calcareous nannofossil counts of ODP Site 207-1260. 202 records from Uncorrected Mg/Ca and sea surface temperature data for Site 165-1000. 13 records from Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 132 records from (Table T2) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049B. 1470 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 289 records from (Appendix B) Nannofossil abundance in ODP Hole 165-998A sediments. 48 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1209A. 3 records from (Table 2) Upper Eocene silicoflagellates from DSDP Hole 95-612. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 3801039 records from FlorKart - FlorenKartierung Gefaesspflanzen. 93276 records from Merseyside BioBank - North Merseyside Flowering Plants (verified). 10254 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 4 records from Pollen analysis of sediment profile PLU01 from Plussee. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 153 records from National Pine Marten Survey of Ireland 2005 - 2007. 132 records from (Table 1) Relative abundances of benthic foraminifera in ODP Site 128-798C. 1921 records from Colección de Algas del Herbario Nacional, Museo Nacional de Historia Natural de Chile. 4240 records from Crustacea collection of National Museum of Nature and Science. 6309 records from University of Lethbridge Herbarium (LEA). 8 records from (Table 3) Characteristics of the Chamelea gallina population on the beach of the Anapa Bay Bar in October 2010. 2353 records from MISE Project Otter Records, 2011-2015. 92 records from (Appendix) Diversity indices of benthic foraminiferal fauna of DSDP Hole 48-401. 895 records from Lichen.ie Data. 58 records from Mamíferos laguna El Tinije. 499 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 1581 records from Colección Ornitológica de la Universidad Industrial de Santander. 25884 records from Colección Nacional de Aracnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 55 records from Molluscan fauna of Gueishan Island of Taiwan. 12809 records from CUMV Fish Collection (Arctos). 58 records from LISU Herbario Angola. 53749 records from Field Museum of Natural History (Zoology) Bird Collection. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 9088 records from Flora of Słowiński National Park, Poland. 509664 records from Museum Victoria provider for OZCAM. 1750 records from Flora of tanzania. 100305 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 2810 records from Helgeland Museum, Araneae. 4972 records from Ohio State University Tetrapod Division - Amphibian Collection (OSUM). 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 61613 records from Atlas of Iberian water beetles (ESACIB database). 117 records from Various insect orders, NEF. 3512 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 3372 records from USGS ASC - Changing Arctic Ecosystems - Alaska - Birds. 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 2126 records from HAS-Algae - Coleção Ficológica do HAS. 7402 records from Helgeland Museum, Lepidoptera. 41 records from CIM Specimens. 568 records from (Appendix 2) Calcareous nannofossils in ODP Hole 189-1172A. 136 records from Plants galls. 41485685 records from Artdata. 2593 records from Mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 16 records from (Table V) Distribution of diatoms in samples from Heidemann Valley trench, Antarctica. 764 records from Scottish Natural Heritage - Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 1905 records from BioGIS - Reptiles - INPA database. 6698 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 1287 records from Harvestmen_of_French_Guiana. 7 records from (Table 4) Characteristics of the Donax trunculus population on the beach of the Anapa Bay Bar in October 2010. 554 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 18643 records from Endemic plants of the Congo basin. 3284 records from Algae (S). 1667 records from Fungus herbarium, UiB. 431 records from Upper Silesian Museum, Insect Collection. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 633712 records from Données ONF Faune-Flore-Fonge. 195 records from (Table T3) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1210A, Shatsky Rise, Pacific Ocean. 3218 records from Road Kill Survey. 283 records from Crustacea ZMK. 1246 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 128-798B. 5116 records from HAMAB - Herbário Amapaense. 710 records from Thames Valley Environmental Records Centre - Natural England Bat Records for Berkshire and Oxfordshire (Held by Thames Valley Environmental Records Centre). 924 records from (Table 15) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-592. 75981 records from Irish Vascular Plant Data - Paul Green. 260 records from SuLaMa reptile survey II 2012. 479 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 2476 records from EcoRecord - Bug (Hemiptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 24280 records from Tromsø Museum, Fungi. 109588 records from UAM Mammal Collection (Arctos). 7 records from A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Rio Caura, Venezuela.. 69 records from (Table 11) Distribution of coccoliths along Core AMK7-786 from the Tajura Rift. 27 records from HSU Wildlife Eggs and Nests. 2 records from Counts of benthos communities in Kongsfjorden in 2009. 540 records from Countryside Council for Wales - CCW Freshwater Fish ad hoc Records for Article 17 Reporting. 14371 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 1095 records from (Figure 3) Distribution of dinoflagellate cysts in the late Albian of DSDP Hole 79-547B. 7348 records from Herbier du Bénin. 1661 records from RSPB - Red-throated diver national surveys in Scotland - raw data (SCARABBS). 1742 records from Eggs Specimen. 513 records from Occurrences des observations de la campagne REMMOA Antilles (2008). 105 records from Landschaftsschutzgebiet Buchhorst 3. 1138 records from (Table T2) Benthic foraminfera stratigraphy of ODP Hole 199-1220B sediments. 51 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 2 records from CCBER Mammalogy Collection. 1 records from Pollen analysis of sediment profile BIB00 from Biber See. 310 records from Lepidoptera collection, NTNU, Trondheim. 1335 records from University of Amsterdam (NL) - Páramo vegetation research, Western Andean Cordillera. 35798 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 3842 records from CRCM Vertebrate Collection. 1612 records from (Figure 8b) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-535. 758 records from Herbario Nacional de Plantas Celulares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 12691 records from MBM - Herbário do Museu Botânico Municipal. 610 records from INRA-Versailles Arabidopsis natural variants. 78804 records from Biological Records Centre - Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 1833 records from (Appendix) Benthic foraminifera distribution of upper Creatceous and Paleocene at DSDP Hole 72-516F. 220 records from International Collection of Microorganisms from Plants - New Zealand National Microbial Collection. 665 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Biodiversity Action Group Brown Hare Survey. 2136 records from Herbario Museo de La Salle Bogotá (MLS). 1662 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campañas 2009-2010. 270 records from Nematode abundance in cold seep sediments of the Nordic Margins (Nyregga, Styregga, Haakon Mosby Mud Volcano). 1023 records from Greater Manchester Ecology Unit - Invasive and Non-native Species From Greater Manchester. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 87 records from Bothrocara nyx: a new species of eelpout (Perciformes: Zoarcidae) from the Bering Sea.. 99816 records from Swedish Malaise Trap Project (SMTP) Collection Inventory. 858 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 3 records from Diatom abundance of Hole 38-338, Part 2. 150 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2011. 14239 records from Cowan Tetrapod Collection - Mammals. 314 records from Peces laguna El Tinije. 11 records from (Figure 4) Distribution of late Paleocene calcareous nannofossils in ODP Hole 132-810C. 69 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 995 records from PSUZC-Amphibians Collection. 73 records from (Table 1) Distribution of Upper Cretaceous agglutinated benthic foraminifers in DSDP Hole 20-196. 2867 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 284 records from Distribution of planktic foraminifera and stable istopes of sediment core MSM05/5_712-2. 285 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 14 records from (Table 2) Abundance of metazoan ice meiofauna in the bottom 30 cm of level sea ice obatined during the 2005 Hidden Ocean expedition. 368 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 246 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 541 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 21142 records from Butterflies of Ireland. 71 records from (Data S1) Palynology of ODP Site 113-696. 16192 records from People's Trust for Endangered Species - Hedgehog records 2005-2006: Hogwatch and Rural Landowner surveys. 6 records from Total meiobenthos abundance from the Crimea shelf, Black Sea, area I. 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 1578 records from (Appendix B) Benthic foraminifera in Indian Ocean surface sediments. 3712 records from Saproxylic Beetles of Ireland. 10584 records from Danish Plant Bugs (Miridae). 28498 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 352 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 297 records from Clyde River Foundation - Bullhead (Cottus Gobio) distribution for Scotland, historical to present. 1652 records from Depletion Fishing in the river "Grote Nete" and "Kleine Nete" (1989-1996). 111036 records from British Phycological Society - Seaweed data for Great Britain and Ireland. 2911406 records from Especímenes INBio. 199 records from MVZ Hildebrand Collection (Arctos). 108 records from (Table 7) Planktonic foraminifera species in bottom sediments of Core ML5_348, North Atlantic. 51 records from Packer Collection / Xenochilicola bees, Chile. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 960 records from (Table 4) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Site 167-1013 sediments. 2 records from New genus of diminutive microhylid frogs from Papua New Guinea. 2303 records from (Appendix) Dinoflagellate abundance in ODP Site 202-1233. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 7416 records from The atlas of breeding birds in Małopolska. 17 records from (Table T4) Calcareous nannofossil abundance of ODP Site 189-1171 sediments. 10326 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Hymenoptera_Bombidae_Types. 252 records from RSPB - Black grouse leks in the Forest of Clunie, 2002-2010 (RSPB, SNH). 16 records from (Table 4) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840C. 2706 records from Alien macro-invertebrates in Flanders, Belgium. 20 records from Description of the males of Euprosthenops australis Simon, 1898 and Euprosthenopsis pulchella (Pocock, 1902) (Araneae: Pisauridae). 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 22978 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 649 records from Countryside Council for Wales - Great Crested Newt (Triturus cristatus) Sites in Wales to 2003. 3382 records from People's Trust for Endangered Species - Hedgehog Hibernation Survey records. 202 records from Inventario de Aves Buenos Aires, Tauramena, Casanare. 55002 records from Biological Records Centre - Reptiles and Amphibians Dataset. 83669 records from Scottish Wildlife Trust - Commissioned surveys and staff surveys and reports for SWT reserves. . 46 records from Hainbachtal in Oelsnitz/V.. 138 records from (Table 1) Late Pleistocene planktonic foraminifera of Hole 302-M0004C. 3800 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 27975 records from Inventaire National du Patrimoine Naturel : Loup en France. 201 records from (Table 1) Benthic foraminiferal genera in DSDP Core 95-612-69. 140 records from (Table 3) Counts of dead (not stained) benthic foraminifera from stations in the northern Gulf of California. 157666 records from Field Museum of Natural History (Zoology) Mammal Collection. 1 records from Reptilia ZMK. 1532 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 3182 records from (Table 15B) Occurrences of planktonic foraminifers in DSDP Hole 90-593, samples 593-31-CC through 593-60-CC. 15925 records from Merseyside BioBank - North Merseyside Other Taxa (verified). 9 records from New provincial records of skinks ( Squamata : Scincidae ) from northwestern Vietnam. 217 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD7. 259 records from (Table 2) Abundances of planktonic and benthic foraminifera in ODP Hole 130-807A. 9006 records from Tallinn Botanic Garden. 271 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 2065 records from The Fossil Fish Collection at the Bayerische Staatssammlung für Paläontologie und Geologie. 5561 records from IWDG Casual Cetacean Sightings. 1091 records from (Table 5) Distribution of benthic foraminifers from ODP Site 134-832. 4 records from Culture Collection of Algae. 50 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 121 records from Stever. 657 records from (Table 2) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Site 133-823. 810 records from Chrysomelidae of the Carpathians. 570893 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 994 records from (Appendix B) Dinoflagellate cysts in Southeast Pacific Ocean surface sediments. 107 records from (Appendix 3) Calcareous nannofossils in ODP Hole 113-690B. 127927 records from OHN. 90 records from (Table 2) Occurrence of larger benthic foraminifers in ODP Hole 133-823C. 223522 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Butterfly data up to current day. 220 records from (Figure 1b) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3182. 162564 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 1 records from Vermes ZMK. 1 records from Description of a new species of Echiodon (Teleostei: Carapidae) from the South Atlantic Ocean.. 6 records from Malakologie ZMK. 965 records from Freshwater plants of Cameroon. 396 records from (Appendix) Bathyal benthic foraminifera in ODP Hole 166-1006A sediments. 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 175 records from Zur Faunistik und Ökologie der Caribiden (Caribidae, Coleoptera) ausgewählter Trockenstandorte in der 'Nuthe-Nieplitz-Niederung' (Land Brandenburg). 3 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 305 records from Wangerooge. 300 records from (Table 3) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Coniacian-Santonian to Albian. 233 records from (Table 3) Relative abundances of benthic foraminifera in chosen time-slices from cores obtained in the Nordic and Barents Seas. 138472 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 808857 records from SA Fauna (BDBSA). 63 records from HSU Wildlife Mammals. 695 records from (Table 5) Benthic foraminiferal community at DSDP Site 94-610. 12002 records from Lund Museum of Zoology (MZLU). 1725 records from (Table 1) Planktonic foraminifer stratigraphy in ODP Hole 167-1021C sediments. 24 records from 10) SST, IRD and benthic foraminiferal d18O data from the Norwegian Sea core MD95-2010: revised chronology for the Last Interglacial (period 134-110 ka). 450 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 31962 records from Herbier de Nouvelle-Calédonie. 2 records from A new candidate for a Gondwanaland distribution in the Zodariidae (Araneae): AustralutIca in Africa. 60 records from Shrews of Poland. 1 records from (List 1) Summary of fossil Mollusca found in Schleswig-Holstein, Germany. 3620 records from Inventaire National du Patrimoine Naturel : Flore protégée du Dauphiné. 102 records from John Muir Trust - A Lichen Survey of the Ben Nevis Plateau. 200 records from Colección de Zoología Invertebrados - Otros invertebrados. 614 records from UCM Bird Eggs/Nests Collection (Arctos). 117 records from A review of Lamyra Loew (Diptera: Asilidae: Laphriinae). 688 records from Algae, Norwegian College of Fishery Science. 48 records from (Table T2) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1136A. 18 records from Survey of the native freshwater opossum shrimp (Mysis relicta) in Ireland. 423 records from (Table 2) Benthic foraminiferal distribution at ODP Hole 127-795B. 411 records from SuLaMa reptile survey I 2012. 5106 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 496 records from (Table 4) Benthic foraminifera in Northwest Indian Ocean surface sediments. 2 records from Ichthyologie ZMK. 71214 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 1489 records from (Figure 4) Dinoflagellate cyst measured on sediment core AI07-03G. 1 records from Ornithologie ZMK. 3 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 27061 records from Bird Monitoring Data. 19 records from Inventaire National du Patrimoine Naturel : Données sur Tamias sibiricus (Ecureuil de Corée). 6518 records from The Fossil Fish Collection at the Jura-Museum Eichstätt. 111 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-8. 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 200 records from Zoological collection of the National Museum. 44 records from (Data S1) Palynology of IODP Hole 318-U1360A. 440 records from NCSM Birds Collection. 1000 records from Colección Limnológica del Chocó. 5605 records from Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 9688 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Pectinoidea. 2 records from Erethistoides sicula, a new catfish (Teleostei: Erethistidae) from India.. 448 records from (Appendix A) Abundance of ostracode species from DSDP Hole 48-401. 495776 records from Bees, Wasps and Ants Recording Society - Bees, Wasps and Ants Recording Society - Trial Dataset. 5 records from FCAB - Herbário Friburguense. 171 records from (Table T1) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049A. 456 records from (Table 1) Mollusc biostratigraphy of a sediment core obtained near Gross Pampau. 3061 records from (Table 4) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-846B. 1933 records from Gloucestershire Environmental Data Unit - Gloucestershire BAP Priority Species - Dormouse. 396127 records from British Lichen Society - BLS Lichen Database: English churchyards. 335 records from Meiofaunal abundance in sediments obtained during RRS Discovery cruise D297. 19084 records from UAM Bird Collection (Arctos). 2234 records from (Figure 1) Dinoflagellate cyst stratigraphy of DSDP Hole 80-548A. 1992 records from (Table 8) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-590A. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 215 records from Umgebung der Grundschule Oderberg. 2 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2010. 803 records from (Table 7) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1020B sediments. 1376 records from Vertical distribution of nannofossils in the section of DSDP Site 72-516. 151 records from (Table T1) Biostratigraphy and distribution of Quaternary and Miocene calcareous nannofossils in ODP Site 188-1165. 6 records from Monomorium dentatum sp. n., a new ant species from Egypt (Hymenoptera: Formicidae) related to the fossulatum group.. 94 records from John Muir Trust - Vascular Plants and Bryophytes of Glen Sligachan. 210 records from (Table 2) Neogloboquadrina plexus coiling direction at DSDP Site 49-410 and Holes 81-552A, 94-610E, and 94-611C. 1150 records from arim. 3313 records from Dorset Environmental Records Centre - Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 1025 records from tef-database. 2080 records from Naturalis National Natural History Museum (NL) – Coelenterata. 1299 records from Waarneming.nl (NL) - Great Grey Shrike Count 2014-2015. 118931 records from Inventaire National du Patrimoine Naturel : Poissons d'eau douce de France. 18 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 65 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 163 records from Entomofauna laguna El Tinije. 378 records from Greater Manchester Ecology Unit - Distribution of Badgers in Greater Manchester. 4817104 records from Bird Ringing Centre in Sweden (NRM). 5311 records from Natural History Museum Maastricht (NL) - Herbarium. 210614012 records from EOD - eBird Observation Dataset. 35 records from Hertfordshire Biological Records Centre - Hertfordshire Otter Records 2002 - 2012. 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 1127 records from Census of the secondary forests of the Lama forest reserve (Southern Benin). 15843 records from Inventaire National du Patrimoine Naturel : Données des campagnes de Suivi Aérien de la Mégafaune Marine (SAMM) de France métropolitaine. 933210 records from Norwegian Biodiversity Information Centre - Other datasets. 2856 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-997A. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 553 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 59 records from CCBER Ornithology Collection. 19 records from (Table S1) Calcareous nannoplankton morphometric analyses performed of Cismon sediment core samples. 12 records from (Appendix B) Stratigraphic occurrence of radiolarian special and species groups in sediments of ODP Hole 199-1218A. 9187 records from Herbarium of the Université Libre de Bruxelles. 1547 records from West Wales Biodiversity Information Centre - Sea Trust Stena Europe Survey of Cetaceans in the St Georgeâs Channel, April 2004- April 2011. 443 records from John Muir Trust - Species Records for John Muir Trust Properties 2007-2009. 1288 records from (Table 4) Distribution of benthic foraminifers from ODP Hole 134-829A. 37 records from Colección de Platyhelminthes del Museo Nacional de Historia Natural de Chile. 1571 records from Banco de Germoplasma del Jardín Botánico Atlántico. 4873 records from Berkshire Reptile and Amphibian Group - BRAG - Berkshire Reptile and Amphibian Records. 1109 records from Gloucestershire Centre for Environmental Records - Gloucestershire BAP Priority Species - Water voles. 9 records from Willersalpe. 4601 records from (Table 2) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Site 79-547A. 67 records from Hertfordshire Biological Records Centre - Roadside Verge Survey 1986 (Herts data from Cambs WT survey). 4339 records from CHAS Mammalogy. 15 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 432 records from Royal Horticultural Society - RHS Hemerocallis gall midge (Contarinia quinquenotata) monitoring. 144 records from Annelida collection of National Museum of Nature and Science. 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 13 records from A revision the Australian species of the ant genus Myrmecina (Hymenoptera: Formicidae).. 8714 records from Greater Manchester Ecology Unit - Bird Records held by Greater Manchester Ecology Unit. 2760 records from ESAS cetacean sightings from 1980 to 2003.. 285 records from Sylva Foundation - European Pear Rust (Gymnosporangium sabinae) monitoring. 15 records from Tardigrada collection of National Museum of Nature and Science. 291657 records from SEAPOP NINA. 5043 records from RSPB - Dartford Warbler national surveys in the UK (SCARABBS). 1656346 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 35445 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 9948 records from Bees of Canada / Gschwendtner property collection. 555 records from (Appendix 1) Abundances of benthic forminifera in ODP Hole 113-689B. 51379 records from Vascular Plant Herbarium, UiB. 637 records from Dinoflagellate cysts in western equatorial Atlantic surface sediments. 17 records from Hazel Dormouse in Ireland. 157292 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 65435 records from CAS Ornithology (ORN). 181 records from Alien Species in Poland - Animals. 19695 records from RAVON (NL) - Fish observations extracted from historic reports 1860-1907. 270 records from Meiofaunal abundance in sediments obtained during RRS Charles Darwin cruise CD179. 34 records from Caddisfly Records, Edenvale, Co. Wexford 2010. 240 records from MPM Herpetology. 8 records from (Table 1) Distribution of benthic foraminifera in GIK_Plankton-B sample. 4452 records from Invertebrate collection of University of Oulu Zoological Museum. 2625 records from (Table 1) Stratigraphic distribution of planktonic foraminifera from the uppermost Miocene to upper Pliocene in ODP Hole 134-832B. 2 records from Pollen analysis of sediment profile MU01 from Muggesfelder See. 10501 records from Naturalis Biodiversity Center (NL) - Cnidaria. 4685889 records from Australia's Virtual Herbarium. 56431 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 91 records from Foraminifera assemblage in surface sediments of the Skagerrak/Kattegat area. 1098 records from RSPB - Great Yellow Bumblebee sightings data in the UK, 1990 onwards (RSPB, BBCT, HBRG).. 1406 records from Colección de mamíferos del Museo de Historia Natural de la Pontificia Universidad Javeriana. 12502 records from The Bat Conservation Trust - Hibernation Survey. 35266 records from Kathryn Kalmbach Herbarium. 3375 records from NMMNH Mammal. 162218 records from Ichthyology Collection - Royal Ontario Museum. 320 records from (Figure 1a) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3180. 1294 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 1200 records from (Table 5) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1014A sediments. 170045 records from CAS Ichthyology (ICH). 3406 records from The Scottish Ornithologists' Club - Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species. 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 8 records from (Table 1) Maximal abundance of dominating species and phytoplankton groups within the Gelendzhik polygon in 2002-2005. 21 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC02. 2952 records from Geneva Herbarium – Burnat Herbarium (G-BU). 7 records from (Table 4) New palynological record of sediments from Odderade. 1602 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in Maastrichtian-Eocene sediments from ODP Hole 189-1172D. 12 records from Naturalis Biodiversity Center (NL) - Mammalia. 746451 records from Museum of Comparative Zoology, Harvard University. 5 records from The genera of the Neotropical armored catfish subfamily Loricariinae (Siluriformes: Loricariidae): a practical key and synopsis.. 8 records from (Table 1) Major and minor element concentrations in the livers of polar bears (Ursus maritimus) from Canada, Alaska and Greenland. 13324 records from Collection of various insect orders, Natural History Museum, University of Oslo. 431 records from Plantas Bosque Seco Chicamocha. 697 records from Herbier de Strasbourg. 33 records from (Table 6) Distribution and abundance of calcareous-nannoplankton species in the Cretaceous sediments of DSDP Hole 62-466. 3319 records from Gloucestershire Centre for Environmental Records - Gloucestershire Amphibians not including great crested newts. 40 records from Diptera collection (ED) of the Muséum national d'Histoire naturelle (MNHN - Paris). 46 records from (Table T2) Stratigraphic distribution of dinoflagellates and pollen/spores by age class, ODP Leg 188 sites. 135412 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 259583 records from USGS PWRC - Native Bee Inventory and Monitoring Lab - US-CA-MX - Bees. 6004 records from Colección Limnológica Universidad de Antioquia. 42 records from (Fig. 4) Relative proportions of the most abundant chironomid taxa in the Lake Temje sediment core. 1 records from Aristathlus imperatorius Bergroth, a newly recognized synonym of Reduvius iopterus Perty, with the new combination Aristathlus iopterus (Perty, 1834) (Hemiptera: Reduviidae: Harpactorinae) ​. 13 records from (Table 2b) Species of planktonic foraminifera found in surface layer bottom sediment at Station Vy20-3217GR. 2473 records from (Table 1) Distribution of planktonic foraminifers at DSDP Hole 90-590A. 860592 records from iNaturalist research-grade observations. 61 records from A new handfish, Brachionichthys australis sp. nov. (Lophiiformes: Brachionichthyidae), with a redescription of the critically endangered spotted handfish, B. hirsutus (Lacepede).. 323085 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 2262 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 94 records from (Fig. 3) Inter-core correlation of Ca/Fe ratios and magnetic susceptibility supported by IRD and N. pachyderma (sin) of sediment core GeoB11035-1. 1 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 1585460 records from NMNH occurrence DwC-A. 17 records from Meiofauna abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 262 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 74 records from SuLaMa reptile monitoring. 493 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 12 records from Dispatch from the field: ecology of ground-web-building spiders with description of a new species (Araneae, Symphytognathidae). 1245 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 16163 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 43298 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 5 records from New species of ant-mimicking jumping spiders of the genus Myrmarachne MacLeay, 1839 (Araneae: Salticidae) from north Queensland, Australia. 1589 records from Aquatic Oligochaeta of Ireland. 1275 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 2824 records from HUCS - Herbário da Universidade de Caxias do Sul. 557853 records from Aranzadi Ringing Scheme (bird ring-recovery data). 56 records from UCM Vertebrate Observations Collection (Arctos). 8399 records from NYSM Birds. 1000 records from Mollusca Specimens of Oiso Municipal Museum. 9399 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 23 records from First record of the genus Venanus (Hymenoptera: Braconidae: Microgastrinae) in Mesoamerica, with the description of two new species from Costa Rica. 1116 records from Colección de Saurios Museo de La Salle Bogotá (MLS). 16504 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Fungi and Lichen Observation Records. Pre-2010 for Cumbria.. 1380439 records from Consortium of California Herbaria. 3 records from New species of myrmicine ants from Western Australia (Hymenoptera: Formicidae).. 49637 records from Monitoring data from the federal state Hesse (Germany). 5506 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 14118 records from Outer Hebrides Biological Recording Project - OHBRP Insects Dataset - Outer Hebrides. 477 records from (Table 2) Distribution of foraminifera in the Miocene section of ODP Hole 133-816A. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 876 records from (Supplement 1) Most common taxa or groups of coccoliths from ODP Site 1233 (past dataset) covering the last 70 kyr. 155953 records from CONN. 2 records from A synoptic review of the ants of California (Hymenoptera: Formicidae).. 1516 records from Fongs d'Andorra. 3541 records from Coleção de Polychaeta do Museu Nacional. 65 records from Taxonomy of the catfish genus Pseudoplatystoma Bleeker (Siluriformes: Pimelodidae) with recognition of eight species.. 2754 records from (Table 7) Benthic foraminifera in middle-late Miocene sediments of DSDP Site 90-590. 366 records from (Appendix A) Abundance of selected coccolithophores in sediment core DS97-2P, North Atlantic. 1321 records from Herbier National de Mauritanie (HNM). 13600 records from Mammal collection, Natural History Museum, University of Oslo. 1 records from A new species of Enoplomischus from Kenya (Araneae: Salticidae: Leptorchestinae). 161 records from John Muir Trust - Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 796 records from Biological Records Centre - Irish Otter Dataset. 1458 records from Waarneming.nl (NL) - Great Grey Shrike Count 2013-2014. 29691 records from University of Amsterdam (NL) – Benthos monitoring of the North Sea research database. 662 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 3381 records from (Table 10B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-588A. 9741 records from Finnish Entomological Database: Hymenoptera. 3669 records from ARKO strandeng. 179 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 89 records from Devon Biodiversity Records Centre - Devon Himalayan balsam data 1997 to 2007. 46 records from Type Collection of the Seto Marine Biological Laboratory, Kyoto University. 1 records from A new ant genus from the southwestern United States.. 102 records from (Table 1) Planktonic foraminifera counts and stable oxygen isotope ratios of Pacific Ocean surface sediments. 40028 records from Recent Invertebrates Specimens. 8 records from First record of Neoempheria Osten Sacken (Diptera, Mycetophilidae) biology in the Neotropical region, with associations between its larvae and fungi. 13720 records from Hemipteran specimens of Iwate Prefectural Museum. 209 records from (Table 2) Ostracoda community from DSDP Hole 95-613. 32 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 50274 records from Plant Specimen from Herbarium (NAS) in China, Institute of Botany, Jiangsu Province and Chinese Academy of Sciences. 80 records from Förderzentrum Schmölln. 589 records from (Appendix B) Benthic foraminifera extinction group polpulation of ODP Hole 184-1146A. 44590 records from Tasmanian Museum and Art Gallery provider for OZCAM. 2 records from Neue Milbenarten aus Kärnten. 914 records from Colección de Coleoptera (Tenebrionidae) del sureste de la Península Ibérica de la Universidad de Granada. 40460 records from Biological Records Centre - Soldier Beetle and Jewel Beetle (Coleoptera; Cantharoidea and Buprestoidea) records for Britain and Ireland to 2000. 1077 records from BioGIS - Fish - HUJ collections. 3 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 2 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 10862 records from Heteroptera of Ireland. 1275 records from (Table T6) Planktonic foraminifera stratigraphy of ODP Hole 198-1209, Zones P12-P18. 2201 records from UFRN-Fungos - Herbário UFRN - Fungos. 47765 records from National Bat Database of Ireland. 66035 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Micro Moths (BNHS) - 1820-2009. 976 records from (Table 2) Benthic foraminifera in Pliocene sediments of DSDP Hole 89-586B. 3002 records from Colección de Peces Universidad Católica de Oriente. 149 records from (Appendix C) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-967A. 175 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 5913 records from An Atlas of Breeding Birds of the Burren and Aran Islands 1993 - 1996. 3546 records from Dorset Environmental Records Centre - Dorset SW Pilot species dataset. 34 records from National System of Protected Areas in Poland - Fungi. 17252 records from BioGIS - Vascular plants - HUJ Herbarium. 10046 records from Biological Records Centre - Crayfish (Crustacea; Astacura) data for Britain and Ireland to 2003. 20893 records from H.A. Stephens Herbarium. 3214 records from Upper Silesian Museum, Bird Observations. 23 records from Cnidaria Collection of the Seto Marine Biological Laboratory, Kyoto University. 1390 records from Caracterización de avifauna de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 2708 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1218A and 199-1219A sediments. 2 records from Discothyrea sringerensis (Hymenoptera: Formicidae) a new ant species from India.. 2877 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 324 records from People's Trust for Endangered Species - Noble Chafer: Post-BAP records from 1998 onwards. 71 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2007. 43 records from A Unique Nest-Protection Strategy in a New Species of Spider Wasp. 121 records from Kloster Eberbach. 1 records from A remarkable new flightless Madrasostes Paulian, 1975 from Vietnam (Coleoptera Scarabaeoidea Hybosoridae Ceratocanthinae). 115 records from RSPB - Bringing Reedbeds to Life Amphibian Survey of two key reedbed sites in England in 2010.. 50000 records from observe_tuna_bycatch_ecoscope. 31 records from Revision of the subgenus Aulacomyrma Emery of the genus Polyrhachis F. Smith, with descriptions of new species.. 202 records from (Appendix A) Relative abundance of benthic foraminifera in ODP Hole 138-844C. 473 records from (Table 1) Foraminifera abundance of ODP Hole 162-985A sediments. 4230 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Coleoptera Records up to Dec 2012. 637 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0002B. 96687 records from Invertebrates Collection of the Swedish Museum of Natural History. 13701 records from AM: Terrestrial Insect Collections (1896-2000). 424 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 33 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto57-65. 86277 records from UCT: Southern African Butterfly Conservation Assessment (1815-2009). 8529 records from NINA botanical collection. 419508 records from Meadow and Pasture Inventory (SJV). 84521 records from BioGIS - Vascular plants - INPA database. 89 records from Arvenses y árboles asociados a cafetales de Cundinamarca. 9490 records from UK Cetacean Strandings Investigation Programme - Stranded cetacean data from Great Britain collected from 01/01/89 through to 31/03/10. 3628 records from Wildbook for Whale Sharks. 1443 records from Odonata of the Congo River 2010 expedition. 14449 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 21 records from Trichoribates and Jugatala (Acari: Oribatida: Ceratozetidae) from the Central and Southern Alps, with notes on their distribution. 70 records from Lech 2001. 252 records from (Table T11) Calcareous nannofossil stratigraphy of ODP Hole 198-1212B. 17 records from Spiders_of_French_Guiana. 6823 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 86 records from Appendix A: Results of the pollen analysis of the PG1755 core from Lake Billyakh. 242 records from (Supplement 3) Dinoflagellate cyst concentrations of the three transects OMZ (GeoB 12312, 12321, 12331), below-OMZ-seep (GeoB 12326), and OMZ-seep (GeoB 12328). 246 records from CaCO3, biogenic opal, TOC, and microfossil observations of sediment core MR06-04_PC23A. 33173 records from Global Lacustrine Diatoms. 45761 records from Estonian Museum of Natural History. 3330 records from Collection botanique Le Grand A. (BOUM). 15973 records from Vegetation data from sheep grazing experiment at alpine site in Hol, Norway. 238 records from John Muir Trust - List of Lichen Species recorded on high ground in the Ben Nevis range. 239 records from University of California Museum of Paleontology. 202161 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 617 records from Meiofauna abundance of westerm Mediterranean Sea seep sediments. 949 records from Percentage analysis of dinoflagellate cyst taxa groups from surface sediment samples of the eastern Indian Ocean. 105 records from (Table 1) Occurrence of Early Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 38393 records from Mammals housed at MHNG, Geneva. 2121 records from HUSC - Herbário Unisanta. 121 records from (Table 2) Relative contents of planktonic foraminifera in bottom sediments from the Ashadze-1 Hydrothermal Field. 40 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto102-110. 164 records from EcoRecord - Flatworm Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 5152 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 9338 records from KUBI Ichthyology Tissue Collection. 1894 records from Fungi Collection. 85 records from Countryside Council for Wales - Welsh Lesser Horseshoe Bat Summer Roost Surveillance Database. 2 records from Male sleeping aggregation of multiple Eucerini bee genera (Hymenoptera: Apidae) in Chapada Diamantina, Bahia, Brazil. 11 records from Pollen profile from sediment core AV14_K2-1. 11 records from Six new species of the spider family Ochyroceratidae Fage 1912 (Arachnida: Araneae) from Southeast Asia. 178 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Records of Fossil Molluscs for Great Britain. 2775 records from Bolivian Amazon lowland fish metacommunity data. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 693 records from (Figure 2e) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3205. 64 records from (Table 4) Pleistocene nannofossil range chart for ODP Hole 134-827B. 405 records from (Table 5) Range chart of benthic and planktonic foraminifera of ODP Site 127-797. 4268 records from Free-living marine Nematodes from Ali, Rada Tilly and El Limite sandy beaches (Chubut, Argentina) 2006.. 148 records from Isarufer. 713 records from (Figure 6) Total organic carbon content and counted dinoflagellate cysts of sediment core GeoB10706-3. 1020 records from National Museum Of Marine Science & Technology. 68 records from RSPB - Bean geese on the Slamannan Plateau, Central Scotland between 1993 and 1995 (RSPB/SNH/Bean Geese Action Group). 238515 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 173033 records from Essig Museum of Entomology. 613 records from Countryside Council for Wales - Shad Monitoring data. 1 records from Pollen analysis of sediment profile BLA00 from Blankensee. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 20 records from Cyatta abscondita: Taxonomy, Evolution, and Natural History of a New Fungus-Farming Ant Genus from Brazil. 6 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2011. 128739 records from Seed and Leaf Beetle Recording Scheme - Bruchid and Chrysomelid Distributions in Britain and Ireland: pre 1900, 1900-1979, 1980 onwards. 122 records from Birdrace_Gütersloher_Gimpel-Gütersloh. 88 records from Birdrace_Die_Polyglotten-Saarlouis. 84 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 59 records from Im Bauerngarten. 241 records from BIRDRACE RennVögel Münsterland. 336 records from Kremmer Luch. 100 records from Feriendorf Ober-Seemen. 56 records from Waldhusener Moor (Lübeck-Kücknitz). 127 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 166 records from Zielbach (Töll). 167 records from Bodenseeufer Radolfzell. 146 records from Steinbruch Mainz-Weisenau. 21 records from Dellwiger Bach (Dortmund). 57520 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 262 records from Natur erleben rund um den Seminarbauernhof Gut Hohenberg. 79 records from Balkon (Norderstedt). 1174 records from Sudeniederung (Amt Neuhaus). 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 257 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 537 records from The French National Collection of forage and turf species (grasses and legumes).. 212 records from (Appendix A) Campanian-Maastrichtian calcareous nannofossils in DSDP Hole 44-390A. 944 records from Circumpolar Seabird Monitoring Plan. 422 records from DMNS Marine Invertebrate Collection (Arctos). 57812 records from ALCB - Herbário Alexandre Leal Costa. 690 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 18 records from (Table 3) Foraminiferal species in DSDP Sample 78-541-5-3,19-21. 118668 records from Estonian University of Life Sciences. 13298 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 2 records from Trichomycterus pauciradiatus, a new catfish species from the upper rio Paraná basin, southeastern Brazil (Siluriformes: Trichomycteridae).. 761 records from Dorset Environmental Records Centre - Dorset Heath - NBN South West Pilot Project Case Studies. 3 records from Revision der Ceratozetidae, 4. Ceratozetes mediocris Berlese (Arach., Acari, Oribatei). 1826 records from Colección de Anfibios Museo de La Salle Bogotá (MLS). 27 records from Tejidos de anfibios y reptiles de la ventana piloto Paz de Ariporo - Hato Corozal. 3327 records from BioGIS - Mammals - SPNI. 39766 records from BioGIS - Vascular plants - A. Danin's point database. 17435 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 33 records from (Table 2) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585A. 22029 records from TNHC Ichthyology Collection. 191 records from Steinbruch Mainz-Weisenau, 2. Jahr. 7 records from (Table 5) Concentrations of organochlorine pesticides in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 2749 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 1244 records from Mosquitoes_of_French_Guiana. 9598 records from Coleccion Entomologica CEI - CCT Mendoza CONICET.. 855 records from (Table 1) Distribution of ostracods in Jurassic sediments of DSDP Hole 79-547. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 23215 records from rmca-albertine-rift-butterflies. 104293 records from mel. 1472 records from Herbarium Rhoenmuseum Fladungen. 189 records from Colección Plantas Vasculares - Herbario del Departamento de Biología, Bioquímica y Farmacia de la Universidad Nacional del Sur. 208 records from (Table 4) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Campanian and Maestrichtian. 15926 records from Derbyshire (Derby Museum) Biological Records Centre - Derbyshire & Peak District Protected Species Database (Summary of available records 1970- 2008). 2432 records from RSPB - Black Grouse Recovery Project Annual Survey in Argyll & Bute 2002-2009 (RSPB/SNH/FCS/Scottish Power). 91 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 1658 records from MISE Project Waterford Otter Records, 2011-2015. 247 records from Quirópteros Asociados al Bosque Seco de la Vereda El Carbonero, Santander de Quilichao, Cauca. 660 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 104 records from Feriendorf des Kreises Gedern (Ober-Seemen). 153 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 161 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-852B. 544 records from Glasgow Museums BRC - The Changing Flora of Glasgow: Orchid Dataset. 8441 records from Natural England - Batsites inventory for England. 23128 records from Monitoring data from the federal state Rhineland-Palatinate (Germany). 87 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 42517 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 13949 records from University of Amsterdam (NL) - Páramo Vegetation Research, Chingaza - Cruz Verde - Monserrate -Guasca, Colombia. 68 records from Occurrence data of Namadytes (Diptera: Asiloidea: Mydidae). 7248 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 169 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 1440 records from (Table 21) Benthic foraminifera in middle Miocene sediments of DSDP Hole 90-594. 12222 records from DMNS Mammal Collection (Arctos). 25 records from Countryside Council for Wales - Freshwater Gwyniad Survey Data. 4 records from Pollen analysis of sediment profile WO1 from Wollingster See. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 114 records from Birdrace-Finkenspötter-München. 112 records from Birdrace_Die_Borner-Viersen. 85 records from Birdrace-Die_Paradiesvögel-Herford. 102 records from Birdrace-Die_Nachtraben-Stuttgart. 76 records from Birdrace-Birding_for_Nature-Bonn. 195 records from FNL e.V.. 113 records from Flora. 143 records from Ehmkendorf. 99 records from Naturgrundstück (Eutin). 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 1340 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Santa Fé de Antioquia, Antioquia (primer censo). 24211 records from Monitoring data from the federal state Saxony (Germany). 1294 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 1836 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 150 records from Birdrace-Ostseevögel-Ostvorpommern. 168 records from Birdrace-Marburger_Vogelwelt.de-Marburg/Biedenkopf. 91 records from Birdrace-Enger_am_Spektiv-Herford. 127 records from Birdrace_Schräge_Vögel-Herford. 103 records from Birdrace-Die_Nachtigallen-Herford. 67 records from Birdrace-Guckers_Offenbach-Offenbach. 33 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from RV Poseidon cruise 334. 134 records from VFD-H: Rheingau: Pferdeweide Loock. 251 records from Seewasen. 351 records from Küstenschutzwald. 95 records from LauWi. 97 records from Grenzturm Hohen Neuendorf. 101 records from Fuchsloch (Mohlsdorf/Ostthüringen). 193 records from Truppenübungsplatz Panzerkaserne Böblingen. 97 records from Döchtbühlwald (Bad Waldsee). 267 records from Regenrückhaltebecken (Zeulenroda). 84 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 157 records from Panke und Ufer am Kinderbauernhof Pinke-Panke. 95 records from Ortelsbruch - Hangmoor bei Morbach. 6072 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 160 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 41 records from Örtzemündung (Stedden). 10 records from Kita-Wäldchen Fuchsturmweg Jena. 94 records from Die Wuhle. 248 records from Geschützter Landschaftsbestandteil - GLB "Troppach". 182 records from Westerwälder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 85 records from Alter Kreidebruch Saßnitz/Rügen. 111 records from Rund um das LUGY. 7 records from (Table T4) Nannofossil counts accross the K/T boundary in ODP Hole 183-1138A. 7356 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Moss and Liverwort Observation Records. Pre-2010 for Cumbria. 251763 records from Moths Ireland. 3 records from Achaeta becki sp. nov. (Oligochaeta: Enchytraeidae) from Amazonian forest soils. 376 records from (Table 1) Distribution of planktonic foraminifera in the Cretaceous succession of DSDP Hole 95-612. 96 records from (Table 2) Neogene benthic foraminiferal community at DSDP Hole 95-613. 819 records from Inventaire National du Patrimoine Naturel : CBN de Midi-Pyrénées. 120 records from Birdrace-Kosmos_Racer-Freising. 18353 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 120 records from Birdrace_Steckbyer-Auenländler-Anhalt_Zerbst. 108 records from Birdrace-TriumVIErat-Viersen. 105 records from Birdrace-ARKONAuten-Rügen. 102 records from Birdrace-Westfälische-Nachtigallen-Recklinghausen. 104 records from Birdrace-Diesmal_sehen_wir_mehr-Lippe. 103 records from Birdrace-Borussia_Zippammer-Bad Kreuznach. 101 records from Birdrace-Herford-Birder-Herford. 99 records from Birdrace-Die_EderSeaWatchers_WsndaH!-Waldeck/Frankenberg. 96 records from Birdrace-federleser-Herford. 94 records from Birdrace-Resopal_Altkreis_Dieburg-Team-Darmstadt/Dieburg. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 92 records from Birdrace-Team_BO-bachter-Bochum. 88 records from Birdrace-WeserEggeLäufer-Höxter. 90 records from Birdrace-Uttenreuther_Spatzenzähler-Erlangen/Höchstadt. 81 records from Birdrace-Breisgau_Brut-Breisgau/Hochschwarzwald. 184 records from Klasse 3a. 162 records from Siegen/ Gymnasium Am Löhrtor. 2 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 83 records from Spechtwald. 268 records from Beweidungsprojekt an der Nesse. 267 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 146 records from Wirbach. 1487 records from (Appendix A) Relative abundance of planktonic foraminifera in ODP Hole 117-723A. 209 records from (Appendix A) Palynofacies absoulte abundances of DSDP Hole 38-338. 638 records from EcoRecord - Fish records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 128 records from Birdrace-Brut-Wetteraukreis. 123 records from Birdrace-Thüringer_Becken-Sömmerda. 118 records from Birdrace-Blind_vor_Birds_BVB_Kranenburg07-Kleve. 111 records from Birdrace-Uhulogen-Lippe. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 110 records from Birdrace-LiLaMai-Vechta. 109 records from Birdrace-Team_Charadrius-Günzburg. 104 records from Birdrace-RMD_Die_Gipfelstürmer-Main-Taunus-Kreis. 100 records from Birdrace-Meister_der_Herzen-Kleve. 97 records from Birdrace-Die_Bonnapartemöwen-Rhein-Sieg-Kreis. 95 records from Birdrace-Buteo1_DO-Dortmund. 72 records from Birdrace-Buteo2DO-Dortmund. 74 records from Birdrace_Gätkes_Schergen-Helgoland. 342 records from Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 34 records from Borkhart. 52 records from Fledermaus. 54 records from Waldsee. 111 records from Hochschulgelände (Bremen). 56 records from Heidesee / Halle. 241 records from Kiesgruben Wemb. 28 records from Hecke - Klassen 2 a und 2 b VS Tussenhausen. 69 records from Schulgarten mit Klasse 8a (Essen). 83 records from Roter Berg Werdau (Leubnitz). 228 records from Föhrenried (Fronreute und Baindt). 260 records from Artenvielfalt Kreis Gießen. 52 records from Caracterización vegetal de una zona de alta montaña (litoral de San Juan) como herramienta de proyección para el establecimiento de una figura de conservación en el chocó biogeográfico. 72 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 310 records from Stadtpark Herzberg (Elster). 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 106 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 66 records from Wedeler Au. 62 records from Kabelskebach (Kabelsketal, Saalkreis). 29 records from Herbarium specimens of Association des Naturalistes de la vallée du Loing (ANVL). 36 records from Berlin - Treptower Park / Karpfenteich. 42 records from "Schlechteberg" Ebersbach/Sa.. 68 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 68 records from Lassentiner Moor (Niepars). 15 records from AKG-Bensheim. 278 records from Deponie Klausdorf. 23 records from Alter Nördlicher Friedhof (München). 20 records from Motzener Tonsee. 75 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 63 records from Gemeinschaftsgarten Deluxe (Bernburg). 44 records from Flusswerder in der Weser (Hameln). 55 records from Zitadelle Berlin-Spandau (7b). 52 records from Wiese am Unterbecken. 9 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 100 records from Naturhausgarten. 180 records from Paul-Gerhardt-Schule Dassel. 110 records from CommunicA Koblenz - Wildkräuterexkursion - Rheinsteig Bornhofer Höhe. 28 records from Nationalpark Harz Schul-AG Braunlage. 48 records from Junge Heide, Radebeul/Dresden. 116 records from Wassermann. 150 records from Landschaftsschutzgebiet "Holmer Sandberge". 73 records from Varnhalt. 59 records from Rund ums Ökohaus (Würzburg). 32 records from Schulhof Sandhofenschule (Mannheim). 122 records from Wiesenbiotop am Wasserturm. 177 records from Spießwoogtal / Königsbruch (Fischbach). 28 records from Sandgrube Zaisertshofen. 61 records from Tag der Artenvielfalt BUND Kaiserslautern. 25 records from Aachen: Exkursion essbare Wildkräuter/UTROPIA. 28 records from NABU VG Weilerbach - NSG Mehlinger Heide, FFH-Gebiet. 97 records from Natur-Erlebnis-Kindergarten Waldkirchen/Erzgebirge. 162 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 294 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 137 records from NSG Leist bei Ziegenhain. 240 records from Gieselbachtal Fulda-Harmerz. 58 records from Artenvielfalt auf der Wiese. 81 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 232 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 94 records from Vielfalt verschiedener Wiesen. 50 records from Weidegut Rechab. 211 records from Binsenwiesen. 300 records from Ried und Sand - Artenvielfalt durch Beweidung. 52 records from Ludwigshofen. 70 records from Bolzplatz. 18 records from Spielwiese. 12 records from Kindergarten. 79 records from GymnQuerfurt. 43 records from Gewässeruntersuchung Grötzinger Baggersee. 54 records from Zentralfriedhof (Wien). 62 records from Erft in Selikum (Neuss). 18 records from Mittelstreifen. 103 records from Wasserwerkspark (Chemnitz). 245 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 100 records from Schwanseepark (87645 Schwangau). 47 records from Trockenrasen bei Dörndorf. 41 records from Wiese und Bach beim Unterbecken (Markersbach). 5 records from Streuobstwiese (Mittelgasse 4). 169 records from Biodiv-Camp Sandmagerrasen in Nürnberg/Langwasser. 97 records from Dorfrand Mauderode. 49 records from Artensuche auf den Elbwiesen in Radebeul. 59 records from Oschenberg, NO von Bayreuth-Laineck. 4 records from Schulbiotop und Brigach (Villingen). 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 28 records from Uferzone Wipper (Biesenrode). 21 records from Breitkopfbecken (Berlin-Reinickendorf). 60 records from Amtsrain Apolda-Zottelstedt. 41 records from Saalewiesen Naumburg. 243 records from WildesMoor bei Schwabstedt. 94 records from Isartal Dingolfing. 92 records from Höltigbaum. 77 records from VFD-RP: Taunus: Ponykoppel Thurner. 158 records from Waldstück Bremerhagen LK Bio Kl. 12. 257 records from Dinocyst occurrences and zonations from IODP Hole 313-M0028A. 60 records from NABUGEO1. 355 records from Carábidos (Coleoptera: Carabidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 10 records from Feuchtwiesen Wippertal bei Wippra. 20 records from Hübsche Kröten, Wetterfrösche und andere Froschnaturen. 94 records from Birdrace-Erlanger_Piepmätzchen-Erlangen/Höchstadt. 86 records from Hartholzaue an der Dreisam (Freiburg/March-Hugstetten). 5 records from Naturschutzgebiet Ahrmündung (Remagen). 53 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 118 records from Birdrace_FliegendeFüchseLBSGescher-Münster. 122 records from Birdrace-Hügelland-Mainz/Bingen. 208 records from Artenvielfalt im Beckerbruch (Dessau). 110 records from Ökologischer Weinberg (Guntersblum). 25 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 35 records from Urwald 3 (Bad Waldsee). 68 records from Schulhof der Astrid-Lindgren-Schule (Elmshorn). 104 records from Außengelände KITA "Mäuseburg" Waldkirchen. 16487 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Compilation of records of rare and scarce species for Great Britain and Northern Ireland. 96 records from Warnowtal (Rostock). 150 records from Selztal bei Friesenheim. 37 records from Flächennaturdenkmal Grubditz. 43 records from Schulgelände Thurmair-Gymnasium. 57 records from Schafsweide Seniorenhaus Berghof. 144 records from NABU-Auerochsenweide. 58 records from Weidewirtschaft. 748 records from Moluscos Marinhos de Augusto Nobre. 60 records from Hochschule Zittau/Görlitz. 163 records from Steinbruch Mainz-Weisenau, 3. Jahr. 141 records from Birdrace-Asiola_Quartett-Nordwestmecklenburg. 9866 records from Dumfries and Galloway Environmental Resources Centre - Micro-moths distribution for Dumfries and Galloway. 110 records from Birdrace-Göttinger_Sozialbrachvögel-Göttingen. 281 records from Hertfordshire Biological Records Centre - Hertfordshire Wildlife Site Monitoring Surveys (incomplete). 53 records from Birdrace-Die_Tigerenten-Erlangen/Höchstadt. 141 records from Kinderbauernhof Pinke-Panke. 16 records from Streuobstwiese Am Kalkofen, Hirschhorn (Kreis Kaiserslautern). 51 records from Steinbachtal (Würzburg). 53 records from Park Schönfeld (Kassel). 36 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 21 records from Tauchen und Meer 02. 22 records from Bachabschnitt der Nette (Osnabrück). 55 records from Mauervegetation,Flechten und anderes. 8 records from Streuobstwiese. 28 records from Stadtpark Prinzengarten (Sigmaringen). 48 records from Heider Bergsee (Brühl). 15 records from Beisetal bei Niederbeisheim. 4 records from Weser und Weseraue bei Höxter, Godelheim und Boffzen. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 23 records from Tümpel Schulbiologiezentrum. 18 records from Wahner Heide - GK 12 Bio Gymnasium Köln-Deutz Thusneldastraße. 18 records from Dachterasse Realschule St. Bernhard (Bad Mergentheim). 97 records from Düne am Ulvenberg (Darmstadt). 157 records from Wirbach-Taubental (Bad Blankenburg). 34 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 76 records from Trockenrasen Franzigmark (Halle/Saale). 27 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 78 records from Umgebung des Spalatin Gymnasium Altenburg. 55 records from Flora und Fauna am Mittelrheintal. 47 records from Weide am Ostufer des Zotzensees, Müritz-Nationalpark. 133 records from Grillhütte Wettsaasen, Wiese, Hecken. 93 records from Kochertgraben II. 68 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 61 records from GE-Brühl. 69 records from Entdeckertour am Muldestausee 1/05. 54 records from Weidegebiete in der Selzrenaturierung. 134 records from Birdrace-Team_Havelland-Havelland. 171 records from Leben im Finkensteiner Moor. 12 records from Naturschutzgebiet Swistbachaue (Eckendorf). 217 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis. 100 records from Birdrace-ImmerWiederhopf-Lörrach. 96 records from Birdrace-Berlin_Sparrows-Uckermark. 23 records from Wiese Niederaula. 102 records from Birdrace-OAG_Neuwerk-Hamburg. 4 records from Anatomical investigation of the slender catshark Schroederichthys tenuis Springer, 1966, with notes on intrageneric relationships (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 25 records from Kinderbauernhof Pinke Panke - Berlin Pankow. 41 records from Morphologische Daten von Natrix. 218 records from Römertal (Steinpleis). 81 records from Stadtpark Schmölln. 44 records from Schulgelände Hans-Carossa-Gymnasium (Berlin). 13 records from Tiere im Teichgebiet. 15 records from Naturschutzgebiet Ahrschleife (Altenahr). 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 18 records from Lerchenauer Baggersee (München). 8 records from Kleiner Ziergarten Winzingen (Neustadt). 15 records from Auf Feld und Wiese / Bretlebener Weg (AWO - Kita Heldrungen). 36 records from Salzwiese Diekskiel. 11 records from Kirschfest (Grundschule Heldrungen) / Kirschberg Oberheldrungen. 112 records from Kaniswall/ Gosener Wiesen an der Spree. 1176 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 103 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 1035 records from Countryside Council for Wales - Rare Flowering Plant and Fern Data. 39 records from Streuobstwiesengelände St.Meinrad Gymnasium. 49 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 300 records from Garten J. Scherrer (Lachen-Speyerdorf). 64 records from Mauernacker (Wettsaasen). 17 records from Schutzgebiet Ochtersum. 22 records from Heilpflanzen im Hainbachtal. 108 records from Obstwiese Osterberg. 191 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 19 records from Goethe-Hauptschule/Projekt I-10. 117 records from Naturschutzgebiet Lochbusch-Königswiesen. 28 records from Hainbachtal bei Oelsnitz / V.. 171 records from Dalbekschlucht. 2 records from Oribatids from Switzerland VII (Acari: Oribatida: Mycobatidae 1) (Acarologica Genavensia XCIX). 95 records from Rund ums Cani. 85 records from Naturerlebnisraum Koppelsberg (Plön). 15 records from Regenwasserabfangsbecken (Erlenbach). 207 records from Biosphäre Bliesgau. 155 records from Birdrace-Usedommeln-Ostvorpommern. 132 records from Wulfsmuehle/Pinnau. 95 records from Landschaftspark St.Leonhard-Deisendorf. 169 records from Birdrace-Cuxland_Schwenke_GeoConsult-Cuxhaven. 100 records from Birdrace-The_Ringers-Friesland. 83 records from Birdrace-Team_Eckhard_Reinstein-Hersfeld/Rotenburg. 113 records from Staatsforst Rehna - Woitendorfer Wald im Biosphärenreservat Schaalsee. 2913 records from Orthoptera (Grasshoppers & Crickets) & allied insects of Ireland. 62 records from Zoo Frankfurt. 31 records from Kurler Busch (Scharnhorst). 44 records from 8c. 63 records from Sternwiese Mülheim-Broich. 53 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 66 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 4334 records from MVZ Bird Observations (Arctos). 26 records from Erhard Sopp. 35 records from Ruhrwiesen Arnsberg, Klasse 9 und 10, Fachbereich Biologie. 101 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 11 records from Waldgebiet Todtnau- Sonnhalde. 80 records from Schulgarten-St.-Georg-Gymnasium. 56 records from Estetal (Buxtehude). 26 records from Schulteich Heinrich-Mann-Schule. 82 records from Mainfränkischer Trockenrasen und Naturschutzgebiet Höhfeldplatte bei Veitshöchheim. 154 records from Bammentaler Duft- und Heilkräutergarten. 90 records from Birkenloh. 106 records from vegoek. 46 records from Neanderthal. 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 190 records from Gelände des Schulzentrums am Himmelsbarg. 83 records from VFD-H: Heidenrod: Pferdeweide Mürth. 46 records from (Table 4) Biomass of (benthic) amphipods in the Bering and Chukchi seas. 127 records from Birdrace-Alb_Donaumoos_Kompetänzteam-Alb-Donau-Kreis. 128 records from Birdrace_turbine_untersee-Konstanz. 110 records from Birdrace-Alle_Vögel_sind_schon_DADA-Uckermark. 39 records from Soolbach-Tal. 120 records from Birdrace-The_early-Birds-Minden/Lübbecke. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 89 records from Birdrace-Team_Wangerooge-Friesland. 101 records from Industriebrache (Kempen). 53 records from Schulgarten Fichteschule. 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 31768 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 829 records from Cambridgeshire & Peterborough Environmental Records Centre - Chippenham Fen Moth surveillance project. 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 87 records from Klütwald. 58 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 40 records from Schulhof Liebfrauenschule Oldenburg. 56 records from Garten in Schmölln. 36 records from Plöwener Wald. 47 records from Schulgelände Ceciliengymnasium. 31 records from Regenwasserabfangbecken. 64 records from Schafheide im Böblinger Wald. 39 records from Regenrückhaltebecken Bad Bevensen. 115 records from Naturschutzgebiet Kochertgraben. 81 records from Streuobstwiese Haus Zeitz. 35 records from Gym Freyung. 27 records from Vögel. 100 records from Hoher Stein Kallenhardt. 137 records from Draubiotop Lavamünd. 23 records from Schulgarten der Hainbuchenschule (Hagenbach). 63 records from Issumer Fleuth. 24 records from Schulgelände der Waldorfschule Vordertaunus in Oberursel. 299 records from (Tables 1-15) Morphometric characteristics of the genus Hinia (Nassariidae, Gastropoda) in the Tertiary of northwest Germany. 77 records from Birdrace-Naturschutzscheune-Darmstadt/Dieburg. 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 79 records from Birdrace-Bielefinken-Bielefeld. 42 records from sbosch. 53 records from Bad Bodenteicher Heide. 13 records from Garten Hamburg Uhlenhorst. 34 records from Selz (Ingelheim am Rhein). 30 records from Blumenwiese und Heckensaum , Kornberg (Gruibingen). 74 records from Steinberg in Heidelberg-Handschuhsheim/Falgen. 1346 records from EcoRecord - Fungi & Lichen records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 39 records from Stausee Weiditz. 63 records from LSG "Großes Bruch". 21 records from Bach. 28 records from Schulgelände Freiherr-vom-Stein-Gymnasium (Hamm). 20 records from Riedkanal Bötzingen. 81 records from Artenvielfalt im Schlosspark Sayn (Sayn/Bendorf). 81 records from Birdrace-Die_Ornithomaten-Herford. 71 records from Birdrace-do_elster_Dortmund. 78 records from Birdrace-Die_Laufenten-Braunschweig. 29 records from Naturerfahrung. 65 records from Schulhof A.-Lindgren-Schule (Elmshorn). 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 49 records from Schrebergarten Düsseldorf Oberkassel. 36 records from Mittelriede Höhe Gliesmarode-Braunschweig. 48 records from Dörnberg. 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 10 records from Ökowerk Emden. 64 records from Pilzlehrwald. 50 records from Mühlenbach bei Buxtehude. 65 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 26 records from Zwickau- Schwanenteich. 31 records from Nationalpark Harz Juniorranger. 19 records from Glemstal (Leonberg). 24 records from Ornithologische Wanderung um Tussenhausen. 10 records from schlittschuhweiher. 27 records from Wiese hinter der Schule (Darmstadt). 20 records from Mikroorganismen. 7 records from Schulhof A.-Schweitzer Schule (Wetzlar). 15 records from Bodentiere rund um die Schule. 64 records from Wiese - Schulgelände des Franziskusgymnasiums (Lingen). 28 records from Insekten. 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 21 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 10 records from Baumbach Arnsberg, Klasse 12, Fachbereich Biologie. 3 records from Naturschutzgebiet Quellgebiet Swistbach (Gelsdorf). 18 records from Naturtag. 9 records from Bachpatenschaft Beeke. 4 records from Sächsische Schweiz (Wehlener Gebiet). 135 records from Waldi-Weiher. 2 records from Stadtrand Berlin - Altglienicke/ Was krabbelt auf unserem Abenteuerspielplatz?. 401823 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 1424 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Flora Vascular Amenazada. 508 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 89 records from Schulgelände Paul-Gerhardt-Schule. 80 records from Landschaftsschutzgebiet Schmutterwald. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 52 records from Naturschutzstation Weinberghaus (Dessau). 447 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 169 records from Expedition "Schulgelände". 517 records from Schulzentrum "Parc Hosingen". 369 records from BIRDRACE Havelland. 269 records from BIRDRACE Kosmos-Racer. 145 records from BIRDRACE Dith Marsh Sandpiper. 144 records from BIRDRACE Die Mohrenlerchen. 69 records from BIRDRACE Pfeifenten. 157 records from BIRDRACE Rheinische Wasserrallen. 78 records from BIRDRACE leucorhö statt logorrhö. 84 records from BIRDRACE Bielefinken. 98 records from BIRDRACE Die Paradiesvögel. 100 records from BIRDRACE Lohmanns Öömi-Studenten. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Akassine*. 103 records from BIRDRACE federleser. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 114 records from BIRDRACE Di-Bi-Di-Birder. 112 records from BIRDRACE Hügelland zu Fuß. 111 records from BIRDRACE Die Wendehälse. 110 records from BIRDRACE Angeliter Ornis. 107 records from BIRDRACE Borussia Zippammer. 23 records from AKG-Gelände in Bensheim. 29 records from Brenz (Heidenheim). 23 records from Ackerrain Plönhagen. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 36 records from Olympiapark (München). 79 records from Lahnufer in Villmar. 24 records from Kaisertal. 21 records from Kaltenkirchen Brache. 12 records from Kinderwald Hannover. 13 records from Warnowufer Groß Klein. 9 records from Wiesendreieck Luckenwalde. 5 records from Feuchtwiese. 8 records from Krittenhorster Wald (Ostkilver). 344 records from Meiofaunal abundance in sediments obtained during Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 42 records from Kleinstbiotop mit Schulteich/Weißwasser. 442 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 13 records from Lauchhamer GEO-Tag der Artenvielfalt. 2 records from Grenzdenkmal Hötensleben - wo früher Grenze wa(h)r - bewahrte Vielfalt. 42 records from NW-Innenhof Gesamtschule Herten 7.6.2001. 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 24 records from Tauchen und Meer. 59 records from Schulteich Freie Waldorfschule Darmstadt. 2 records from Hildener Heide - Spörkelnbruch (Haan). 163 records from Tiere und Pflanzen am Pfannenbach. 6 records from Boimstorfer Sundern. 1 records from 5. Wiener Gemeindebezirk. 371 records from Bannwald Burghauser Forst. 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 318 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 93 records from Haarbach Höfe. 74 records from Schulwald Grundschule Brügge. 274 records from Bernhardsthal. 90 records from VFD-RP: Taunus: Kirchenweide Köpplers. 366 records from Weinberg Reichersdorf. 249 records from BIRDRACE DEVK-Deutschlands Enthusiastischste Vogel Kucker. 313 records from BIRDRACE Gätkes Erben. 272 records from BIRDRACE Niederlausitz-Team. 274 records from BIRDRACE Asiola-Quartett. 256 records from BIRDRACE Upupa epöpse. 13 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 16 records from Im und um das Schulhaus. 21 records from LBV-Kindergruppen Markt Tussenhausen. 11 records from Privatteich(St.Leon). 27 records from Bäche im Mooswald (Vörstetten). 12 records from Ohemoor (Hamburg/Norderstedt). 12 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 5 records from Streuobstwiesengebiet (Kreis Ahrweiler). 2 records from LSG Saale, Rößewiesen (Bernburg/Saale). 1 records from Wiese, Wiesengebiet, Schiffdorfer Damm. 60 records from Rotes Steigle (Panzerübungplatz Böblingen). 1 records from Karpfenteich, Klasse 6d. 123 records from Total living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >30 µm. 65 records from Total living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >30 µm. 66 records from Total living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >30 µm. 126 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, >125 µm fraction. 46 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 63-125 µm fraction. 10 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 30-63 µm fraction. 2 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 30-63 µm fraction. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-03, >125 µm fraction. 50 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 4 records from "Am Riedert" im Westerzgebirge. 12 records from FND "Weißer Berg" Leißling. 5 records from Fließgewässeruntersuchung am Haselbach. 3 records from FFR Hausen. 44 records from Georgs-Padd (Wangerooge). 13 records from Kleinsäuger der Mergelgruben Misburg (Hannover). 8 records from Mit allen Sinnen durch den Wald / Schmücke (ev. Kita Heldrungen). 5 records from Naherholungsgebiet Lange Erlen (Riehen/Basel). 23 records from Wattuntersuchung (Cuxhaven). 34 records from Wattenmeer-Safari (Wurster Watt). 17 records from Tierpark Zittau. 5 records from Sächsische Schweiz (Pfaffenstein). 41 records from Nachtaktiv im Ökogarten (Bad Waldsee). 16 records from Kohlbach (Sulzfeld). 15 records from Urwald 2 (Bad Waldsee). 15 records from Tiere. 87 records from Landschaftsschutzgebiet Buchhorst 4. 8 records from Eichendorf Weiher Schwalbach a.Ts.. 16 records from Naturschutzgebiet "Gellener Torfmöörte" (Landkreis Wesermarsch). 5 records from Schulinnenhöfe (Gelsenkirchen). 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 11 records from Vögel im Garten Kindergarten Zaisertshofen. 3 records from Blankenfelder See. 5 records from Fledermäuse u. nachtaktive Insekten. 295 records from (Table 3) Range chart of benthic and planktonic foraminifera of ODP Site 127-795. 255 records from Colecciones Zoológicas de la Universidad de León, Colección de Bivalvos. 24098 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Anfibios. 88956 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Mamíferos. 1095 records from Dpto. de Zoologia y Antropologia Fisica, Universidad de Murcia. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 61 records from Fürstenberger Ralley Teil 3. 107 records from Müritz-Nationalpark. 1506 records from (Appendix C) Benthic foraminifera extinction group species in combined ODP Site 162-980 and DSDP Site 80-548. 15 records from Kühnauer Aue und Kühnauer See. 359 records from Pöhlberg bei Annaberg. 40 records from Glacial cold-water coral: ages, isotope concentrations and ratios. 1 records from Graureiher in Lans. 22 records from Altendorfer Dorfbachhöhle / Sächsische Schweiz. 39 records from Tiere und Pflanzen um uns herum !. 15 records from Kirchheller Heide ( Bottrop). 7 records from Stadtrandlandschaft Apolda-Nord. 12 records from Schulgelände Erich-Kästner-Schule. 1 records from Waldtag in und um Seelingstädt. 5 records from Schulhof Montessori Schule (Rotenburg / Wümme). 1 records from Haslauer Moor. 1 records from Fledermäuse über der Alster (Hamburg). 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 15518 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Peces Continentales. 36245 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Reptiles. 555 records from FFH-Gebiet "Calwer Heckengäu". 13 records from Tag der Artenvielfalt am Bruckenwasen. 2814 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 60 records from Pollen and age analysis of terrestrial plant wax from ODP Hole 175-1085A. 146 records from LK 11 im Mönchspark. 106 records from VFD-RP: Eifel: Orchideenweide Ankly. 126 records from Schulwald Marksuhl. 161 records from BIRDRACE Nord-Seh-Team. 334 records from BIRDRACE Cuxland - Schwenke Geo Consult. 278 records from BIRDRACE Usedommeln. 442 records from Inventaire National du Patrimoine Naturel : CBN Brest. 279 records from BIRDRACE Wannacks Topti(c)ker. 287 records from BIRDRACE Pody und Co. 140 records from BIRDRACE Guckers Offenbach. 80 records from BIRDRACE Falkenberger Fluppis. 102 records from BIRDRACE Willi goes Birding. 102 records from BIRDRACE Westfälische Nachtigallen. 106 records from BIRDRACE Die Göttinger Sozialbrachvögel. 123 records from BIRDRACE INTERNETLITHO feat Fliegende Füchse. 112 records from BIRDRACE Gütersloher Gimpel. 260 records from (Table T5) Biogenic and mineral composition of sediments cored in Westerland, Sylt. 280 records from BIRDRACE Alb-Donaumoos-Kompetänzteam. 258 records from BIRDRACE Raumpatrouille Oriolus. 89 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 118 records from BIRDRACE Die Lippegeier. 82 records from BIRDRACE Die Ziegeneier. 166 records from BIRDRACE Die Düsselmöwen. 91 records from BIRDRACE NABU LV Hessen. 91 records from BIRDRACE SchrägeVögel. 96 records from BIRDRACE OAG Neuwerk. 96 records from BIRDRACE Emslandracer. 100 records from BIRDRACE Stuttgart 100 trööt. 101 records from BIRDRACE Enger am Spektiv. 104 records from BIRDRACE Erlanger Piepmätzchen. 104 records from BIRDRACE Die Marburger-Vogelwelt.de radelt. 79097 records from All Ireland Non-Marine Molluscan Database. 105 records from BIRDRACE coesfelder_vogelkundler. 132 records from BIRDRACE Die Wetterauer. 123 records from BIRDRACE Unterste Niederrhein-Rennvögel. 119 records from BIRDRACE Tick, Trick und Track. 114 records from BIRDRACE VIE will rock you!. 109 records from BIRDRACE Die Borner. 108 records from BIRDRACE Diesmal sehen wir mehr. 277 records from Naturschutzgebiet Börstig bei Hallstadt. 402 records from Tag der Artenvielfalt in Heidelberg. 44 records from Wiesen am Treffpunkt Freizeit. 66 records from Langes Tannen(LMS), Klasse 5d. 37 records from Liether Park 2 (LMS), Klasse 6c. 62 records from Hettstadt Gehäge. 234 records from Wiesen-Wälder-Wasser um Dansenberg, Biosphärenreservat Pfälzerwald. 54 records from Biotope im Schulumfeld. 132 records from Aachtobel. 194 records from Bodenteicher Seewiesen. 264 records from Artenvielfalt im Naturschutzgebiet an der Loreley - Leiselfeld/Spitznack - 2. Jahr. 85 records from Ober-Olmer Wald. 214 records from Pflanzen und Tiere im Burgwald. 49 records from VFD-H.: Rheingau: Bärstadt. 58 records from VFD-H. Heidenrod: Mähweide im Wasserschutzgebiet. 269 records from BIRDRACE speedbirder. 269 records from BIRDRACE Dithmarscher Deichhühner. 50 records from BIRDRACE Schwarzstorchbruthöhlen-Initiative Rügen. 103 records from BIRDRACE Resopal-Darmstadt-Dieburg. 254 records from BIRDRACE Thüringer Becken-Birders. 138 records from BIRDRACE Arkonauten. 65 records from BIRDRACE Federal Birds of Investigation FBI. 15339 records from Alterra (NL) - Comparison entomofauna in cities en countrysides. 82 records from BIRDRACE Buteo2DO. 84 records from BIRDRACE Avinauten. 95 records from BIRDRACE BiBi. 95 records from BIRDRACE accipiter hardcore birding. 97 records from BIRDRACE NABUhu Trier!. 99 records from BIRDRACE TEAM BO-BACHTER. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Bkassine*. 102 records from BIRDRACE Buteo1DO. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Ckassine*. 103 records from BIRDRACE Die Otzberger. 105 records from BIRDRACE Kiesmätze. 174 records from BIRDRACE Bon(n)apartemöwen. 106 records from BIRDRACE Ave Goettingen!. 106 records from BIRDRACE EFTAS-NLU Birdrace Team 2008. 134 records from BIRDRACE Griffin Wood Warblers. 131 records from BIRDRACE Brut. 149 records from BIRDRACE Birding Bentheim. 126 records from BIRDRACE Duckehühnchen. 120 records from BIRDRACE The early birds. 58771 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 115 records from BIRDRACE Die UHULOGEN. 67 records from Tongrube bei Hettstedt. 145 records from Gronau - auf der Suche nach dem Neunauge. 504 records from Schatzinsel Wangerooge. 144 records from Lustbach-Umland. 54 records from Königsdorfer Wald. 73 records from VFD-HH/SH: Pferdweide Lammert. 106 records from NSG Forst Zinna-Jüterbog-Keilberg. 113 records from Tornoer Teich. 144 records from VFD-RP: Hunsrück: Pferdeweide Kucher. 54 records from VFD-H: MIttelgebirgsweide. 99 records from Streuobstwiese Stedar. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 120 records from VFD-H: Heidenrod: Beckers Weide mit Wald. 248 records from Schulgarten der Volksschule. 80 records from Feldweg Waldkirchen. 2 records from Neue Oribatiden (Acari) aus Deutschland III. Suctobelba carcharodon n. sp. und Suctobelba prominens n. sp.. 101 records from Steinbruch Kronungen. 96 records from "Ahrschleife bei Altenahr". 4500 records from (Figure 7) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-540. 121 records from BIRDRACE Immerwiederhopf. 107 records from BIRDRACE Herford Birders. 121 records from Owere Fiddel. 114 records from Liether Kalkgrube. 62 records from Lebensraum Dorf. 61 records from Wälder im Hainbachtal. 85 records from Rund um den Hainbergsee. 83 records from BIRDRACE Die Frankenpfeifer. 106 records from BIRDRACE Die Schwenker-Birder. 104 records from BIRDRACE Andechser Stativträger. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 110 records from BIRDRACE Linumer Luchschleicher. 18 records from Landschaftsschutzgebiet Buchhorst2. 1964 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 31 records from Düpenauwiesen. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland 2. 6325 records from Colección Entomológica de la Universidad de Antioquia. 99 records from VFD HH/SH "Pferdeweide Lemsahl". 40 records from BUND Naturschutzzentrum St. Julian. 45 records from Reusaer Wald. 12 records from Art´n Vielfalt im Kinderwald. 42 records from Feuchtwiese Grüne Mitte, Klasse 5a. 82 records from Teich im Wald zwischen Böblingen und Schönaich. 24 records from Klassenfahrt Usedom / Wald und Küste in Zinnowitz. 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 43 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 63-125 µm. 53 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 87 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, >125 µm fraction. 530 records from Benthic foraminifera counts of sediment core GIK23352-3. 173 records from FFH-Gebiet Klosterwasser/Burkau. 709 records from "Laubenheimer Bodenheimer Ried" - von Stromtalwiesen und Flutrasen. 116 records from Sürther Aue. 83 records from VFD-H: Heidenrod: Weide am Ortsrand. 88 records from BIRDRACE Kingfisher. 334 records from (Appendix 2) Stratigraphic distribution of key and potential stratigraphic calcareous nannofossil markers in the upper Campanian-Maastrichtian of ODP Hole 122-762C. 120 records from BIRDRACE Ornis im Einsatz. 94 records from FFH-Gebiet Paartal. 30 records from Geführte Wanderung im Eselsbachtal. 75 records from BIRDRACE Die Kartoffelsäcke. 84 records from BIRDRACE Vogelscheuchen. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland. 30 records from Leben auf einer Sturmfläche. 18 records from Schulgarten der Gesamtschule Am Heidberg. 7685 records from European riparian ground beetles. 2179 records from (Table 7) Absolute abundances of benthic foraminifera in Neogene sediments of DSDP Site 90-588_Site in the southwest Pacific. 61 records from (Table 1) Sedimentology of core D11957P. 52 records from Sedimentology and stratigraphy of core OD96_41:4:1. 159 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction >125 µm. 35 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 63-125 µm. 250 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Cetacean data up to current day. 14 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 63-125 µm fraction. 31 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-18. 54 records from Wir erkunden die Hofau, Klasse 5c. 29 records from Waldwiese. 36 records from Artenvielfalt in der Quälingsbachaue Gladbeck. 66 records from Von der Nutzung zur Natur. 36 records from Liether Park 1 (LMS), Klasse 5b. 61 records from BIRDRACE Baumläufer. 76 records from BIRDRACE Nachtigallen. 79 records from BIRDRACE Blinde Hühner. 84 records from BIRDRACE Birding for Nature. 143 records from BIRDRACE Die Laufenten. 89 records from BIRDRACE Uttenreuther Spatzenzähler. 90 records from BIRDRACE TicTacToe. 177 records from BIRDRACE Mehr Seh Team. 101 records from BIRDRACE nabu-rhein-main.de. 102 records from BIRDRACE Niederrheinische Bartgeier. 114 records from BIRDRACE LiLaLau. 277 records from Colección de Entomología - Auchenorrhyncha. 27 records from Schulgarten Waldorfschule Hassfurt. 69 records from Unter hellen Zinnen und finsteren Grotten. 47 records from Schulgelände Grolland. 69 records from BIRDRACE Mathilden-Käuze. 88 records from BIRDRACE Vogelkucker. 21 records from Sonntagmorgen-Veranstaltungen im Zeichen des GEO-Tags. 17 records from Bachrenaturierung Littfe. 35 records from Scottish Natural Heritage - Information on capercaillie distribution collected during the âProductivity of breeding Capercaillie Tetrao urogallus at sites across their Scottish range 2011â monitoring project.. 53 records from BIRDRACE Taubenhaucher. 152 records from BIRDRACE NAJU-Aspach. 33 records from Schüler erforschen die Helme-Aue. 2483 records from NX - Herbário Nova Xavantina. 146 records from BIRDRACE VdW Wilder Westen. 63 records from Rosarium (LMS), Klasse 6a. 64 records from Rechts des Inn Höhe Hofau Rosenheim. 13 records from Vergleich der Fauna eines naturbelassenen mit einem wasserwirtschaftlich veränderten Gewässer. 30 records from Riekdahler Wiesen. 17 records from Nachtinsekten am Muldenufer. 18 records from GEO-Tag der Artenvielfalt der Klasse 7c am Gymnasium Allee im Wohlers Park. 30 records from Höhle am Neuweg / Sächsische Schweiz. 51 records from Kindervilla Außengelände. 12 records from Flora und Fauna am Mühlberg. 77 records from VFD-RP: Taunus: Mähweide Dehe. 192 records from "Schwarzwassertal" bei Pobershau. 1 records from Streuobstwiese Alt Necheln. 176 records from BIRDRACE Professorenteam. 120 records from BIRDRACE Die TUErteltauben. 3 records from Rivulus sape, a new species of killifish (Cyprinodontiformes: Rivulidae) from the Paragua River system, Caroní River drainage, Guyana Shield, Venezuela.. 57 records from Schulgarten Janusz-Korczak-Realschule. 184 records from Chinese species of egg-parasitoids of the genera Oxyscelio Kieffer, Heptascelio Kieffer and Platyscelio Kieffer (Hymenoptera: Platygastridae s.l., Scelioninae). 48 records from Wahner Heide LK 12 Biologie. 52 records from Aktion der Klasse H2 in Simmelsberg. 38 records from Aktionstag "Artenvielfalt der Feuchtwiesen bei Daubringen". 38 records from Was lebt in der Brutzwiese?. 58 records from Schulgarten Zinnowwald-GS. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 7 records from Die Bachspezies. 11 records from Umgebung Jugendherberge Clausthal, Klasse 8d. 66 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2137-1. 9126 records from (Appendix 3) Assemblage of benthic foraminifera in sediment core M5/2_KL15. 31 records from Benthic foraminifera counts of sediment core PS2644-2. 117 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >125 µm. 54 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >125 µm. 46 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 63-125 µm. 22 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 63 records from Plasm bearing foraminifera counts of multinet SO117_MSN1245. 259 records from Benthic foraminifera accumulation rate and benthic foraminiferal productivity proxies at ODP Site 165-999 in the Caribbean (Appendix A). 64 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 88 records from Abundance of benthic foraminifera in late Paleocene to eraly Pliocene sediments of DSDP Hole 74-525A on the Walvis Ridge, South Atlantic (Table 1). 5477 records from Colección de mamíferos de la Universidad del Valle. 1077 records from The Bat Conservation Trust - Bechstein's Bat Survey Project. 930 records from Benthic foraminifera counts of sediment core PS2644-5. 59 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction >125 µm. 25 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >125 µm. 26 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraczion 63-125 µm. 43 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 63-125 µm. 39 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 30-63 µm. 8 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 30-63 µm. 127 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 17 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 30-63 µm. 26 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 563 records from NRM-Herpetology. 27 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, >125 µm fraction. 37 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, >125 µm fraction. 35 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 214 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-43. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-03, 63-125 µm fraction. 13 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 30-63 µm fraction. 349 records from Benthic foraminiferal assemblage in the 125-250 micron fraction of sediment core PS1745-5 (Table 5). 541 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 61 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 5110 records from Live benthic foraminifera in South Atlantic surface sediments. 663 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 116 records from Abundance of dead benthic foraminifera in sediment core CD86_05_BC5. 521 records from Bayerische Donau - Leipheim. 108 records from Total living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction >30 µm. 158 records from Total living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >30 µm. 192 records from Total living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction >30 µm. 18 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, >125 µm fraction. 35 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, >125 µm fraction. 56 records from (Appendix A) Pollen and spore counts at DSDP Hole 64-480. 16 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 63-125 µm fraction. 76 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, 63-125 µm fraction. 27 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 30-63 µm fraction. 33 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, 30-63 µm fraction. 85 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 56 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-02. 68 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-04. 827 records from Schatzinsel Norderney. 75 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 31 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 143 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 63-125 µm fraction. 54 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction. 56 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 30-63 µm fraction. 114 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-52. 10 records from Monitoring of Nigritella nigra in the Kvikne mountains, Tynset, Norway. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 63-125 µm fraction. 273 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core GIK17728-1 (Table 4). 421 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core GIK17728-1 (Table 7). 545 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core PS1745-5 (Table 8). 169 records from Benthic foraminifera assemblage in sediment core BBLL2_MC1. 212 records from Benthic foraminifera assemblage in sediment core BBLL3_MC1. 128 records from Benthic foraminifera assemblage in sediment core BBLL2_MC4. 48 records from Assemblage of living benthic foraminifera in sediment profile GeoB4901-6. 152 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-35. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-14, >125 µm fraction. 216 records from (Table 2a) Downcore distribution of live benthic foraminifera of sediment core PS1394-1, Weddell Sea. 68 records from Review of the genus Namadytes Hesse, 1969 (Insecta: Diptera: Mydidae: Syllegomydinae). 316 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23068-3 in the Norwegian Sea. 576 records from Distribution of agglutinated foraminifers in sediment core Well 6407/9-3. 329 records from Benthic foraminifera counts of sediment core GIK23351-1. 2416 records from Upper Aptian Serre Chaitieu (Niveau Fallot) benthic foraminifera. 781 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 3570 records from Total fauna of benthic foraminifera of sediment core Kronsmoor, Late Cretaceous. 2196 records from Total fauna of benthic foraminifera of Hole 44-390A, Blake Nose Plateau, North Atlantic. 118 records from Abundance of dead benthic foraminifera in sediment core CD86_03_BC4. 112 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 53 records from Abundance of living benthic foraminifera in sediment core CD86_09_BC1. 345 records from Diversity of benthic foraminiferal faunas and benthic foraminifera accumulation rates of ODP Site 184-1143. 149 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 141 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC2-L, size fraction >150 µm. 96 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-51. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, >125 µm fraction. 33 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-14, 63-125 µm fraction. 10 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-03, 30-63 µm fraction. 45 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-09. 145 records from Assemblage of living benthic foraminifera in sediment profile GeoB4909-4. 2 records from Balantiocheilos ambusticauda, a new and possibly extinct species of cyprinid fish from Indochina (Cypriniformes: Cyprinidae).. 998 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23414-9 in the Norwegian Sea. 733 records from Distribution of agglutinated foraminifers in sediment core Well 6406/8-1. 394 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 773 records from Distribution of calcareous foraminifers in sediment core Well 6406/11-1. 278 records from A revision of Malagasy species of Anochetus Mayr and Odontomachus Latreille (Hymenoptera: Formicidae).. 333 records from Distribution of calcareous foraminifers in sediment core Well 6407/7-2. 294 records from Distribution of calcareous foraminifers in sediment core Well 6407/9-3. 790 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_100MC. 291 records from Benthic foraminifera counts of sediment core GIK17730-4. 346 records from Benthic foraminifera counts of sediment core GIK23342-6. 448 records from Benthic foraminifera counts of sediment core GIK23359-2. 356 records from Biotope in Rheine - Aktion 350. 41 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 684 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core PS1906-1 (Table 9). 124 records from Benthic foraminifera assemblage in sediment core BBLL3_MC2. 108 records from Assemblage of living benthic foraminifera in sediment profile GeoB4906-5. 335 records from (Appendix 6) Benthic foraminifera at termination II in sediment core PS1906-2 in the Greenland Sea. 945 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23414-9 in the Norwegian Sea. 553 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 852 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_88MC. 874 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_98MC. 357 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 549 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S6 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 129 records from Abundance of living benthic foraminifera in sediment core CD86_01_BC1. 50 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 58 records from Abundance of living benthic foraminifera in sediment core CD86_08_BC5. 21548 records from Benthic foraminifera abundance of ODP Site 184-1143. 31 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, size fraction >150 µm. 2 records from Haselbachtal. 140 records from (Table 2b) Downcore distribution of live benthic foraminifera of sediment core PS1394-3, Weddell Sea. 1 records from Opamyrma hungvuong, a new genus and species of ant related to Apomyrma (Hymenoptera: Formicidae: Amblyoponinae). 430 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23068-3 in the Norwegian Sea. 412 records from Benthic foraminifera counts of sediment core GIK23063-3. 432 records from Benthic foraminifera counts of sediment core PS1246-4 (GIK23246-4). 376 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_91MC. 331 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_93MC. 358 records from Counting of planktic foraminifera of ODP Hole 182-1129C. 407 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Buchaugraben in the Lower Inn Valley area. 126 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 289 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S5 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 3492 records from Species counts of benthic foraminifera of sediment core BOFS5K. 192 records from (Table AT1) Grain size distribution and stable isotope record of benthic foraminifera of ODP Hole 175-1085A. 38 records from Abundance of dead benthic foraminifera in sediment core CD86_07_BC4. 110 records from Abundance of dead benthic foraminifera in sediment core CD86_08_BC5. 253 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23256-1 in the Arctic Ocean. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 94 records from Distribution of calcareous foraminifers in sediment core Well 6406/8-1. 397 records from Benthic foraminifera counts of sediment core GIK23353-5. 936 records from Benthic foraminifera counts of sediment core PS1852-1 (GIK21852-1). 370 records from Benthic foraminifera counts of sediment core PS1244-2 (GIK23244-2). 656 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_107MC. 2416 records from Upper Aptian Serre Chaitieu (Niveau Fallot) counts of benthic foraminifera, SE France. 451 records from Counting of benthic foraminifera of ODP Hole 182-1132B. 172 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 431 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 482 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 1242 records from Lower Albian Moriez core (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 745 records from Counts of the dead benthic foraminifera assemblage in surface sediments of the North Atlantic. 1550 records from Species counts of benthic foraminifera of sediment core BOFS14K. 477 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 596 records from Lower Albian l`Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 637 records from Counts of the living benthic foraminifera assemblage in surface sediments of the North Atlantic. 68 records from Abundance of dead benthic foraminifera in sediment core CD86_01_BC1. 89 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction 63-150 µm. 79 records from Benthic foraminiferal assemblage (dead) in MUC OB10-K, size fraction >150 µm. 313 records from Benthic foraminiferal assemblage (dead) in MUC SC1-K, size fraction >150 µm. 274 records from Benthic foraminiferal assemblage (dead) in MUC SC2-L, size fraction >150 µm. 918 records from (Fig. 4) Assemblage of benthic foraminifera in sediment core GeoB6725-1. 5 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, >125 µm fraction. 180 records from Assemblage of living benthic foraminifera in sediment core GeoB3701-1. 141 records from Assemblage of living benthic foraminifera in sediment core GeoB3702-2. 131 records from Assemblage of living benthic foraminifera in sediment core GeoB3715-1. 152 records from Faunal assemblage of sediment core TR149-38b. 5438 records from (Appendix A) Benthic foraminiferal assemblages in sediments of the last 550 kyr of ODP Hole 130-807A from the Ontong Java Plateau, Pacific Ocean. 734 records from Stable oxygen isotope ratios of foraminifera from late middle Eocene sediments of ODP Site 171-1052 from Blake Plateau, West Atlantic Ocean (Appendix). 81 records from Plasm bearing foraminifera counts of multinet SO118_MSN1251. 67 records from Total foraminifera counts from M35/1_MSN1056. 83 records from Abundance of living benthic foraminifera in sediment core CD86_02_BC5. 65 records from Abundance of living benthic foraminifera in sediment core CD86_05_BC5. 41 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 62 records from Abundance of living benthic foraminifera in sediment core CD86_10_BC4. 1431 records from (Figure 6) Benthic foraminifera counts of sediment core MD01-2378. 12 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 2. 57 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC2-L, size fraction 63-150 µm. 2210 records from Merseyside BioBank - North Merseyside Mammals (unverified). 2040 records from Perthshire Black Grouse Study Group (PBGSG) - Black Grouse annual lek counts in Perthshire 1990-2009 (Perthshire Black Grouse Study Group). 20 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, >125 µm fraction. 25 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC464. 41 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC469. 42 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 30-63 µm fraction. 4 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, 30-63 µm fraction. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, 63-125 µm fraction. 101 records from Assemblage of total living benthic foraminifera in sediment core SO119_MC501. 18 records from Assemblage of living benthic foraminifera in sediment core CD145_55808#3, >150 µm. 201 records from Assemblage of living benthic foraminifera in sediment core GeoB4912-4. 66 records from Abundance of living benthic foraminifera in sediment core CD86_03_BC4. 58 records from Abundance of living benthic foraminifera in sediment core CD86_04_BC4. 33 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 3. 203793 records from Joint Nature Conservation Committee - Marine benthic dataset (version 1) commissioned by UKOOA. 77 records from Benthic foraminiferal assemblage (dead) in MUC SC1-K, size fraction 63-150 µm. 49 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 7 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 30-63 µm fraction. 16 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 9 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, >150 µm. 23 records from Assemblage of living benthic foraminifera in sediment core CD145_55802#4, 63-150 µm. 24 records from Assemblage of living benthic foraminifera in sediment core CD146_55916#1, 63-150 µm. 40 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, 63-150 µm. 67 records from Number of live benthic foraminifera in Nordensheld Bay, Novaja Zemlja. 28 records from Counts of recycled Pliocene foraminifera of sediment core CRP-1 (App. 1). 320 records from Assemblage of living benthic foraminifera in sediment core GeoB3712-1. 267 records from Assemblage of living benthic foraminifera in sediment core GeoB3713-1. 166 records from Assemblage of living benthic foraminifera in sediment core GeoB3725-1. 2233 records from Chrysomelidae of Poland. 89 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, size fraction 63-150 µm. 43968 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Vertebrate Observation Records, other than Birds. Pre-2010 for Cumbria. 55 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 63-125 µm fraction. 27 records from Assemblage of living benthic foraminifera in sediment core CD145_55802#4, >150 µm. 16 records from Assemblage of living benthic foraminifera in sediment core CD145_55818#4, >150 µm. 11 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, >150 µm. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, 63-150 µm. 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 134 records from Number of dead benthic foraminifera in Nordensheld Bay, Novaja Zemlja. 69 records from (Table 3) Downcore distribution of live benthic foraminifera of sediment core SW_2b, California continental borderland. 101 records from (Table 4a) Downcore distribution of live benthic foraminifera of sediment core SW_3a, California continental borderland. 65 records from (Table 4b) Downcore distribution of live benthic foraminifera of sediment core SW_3b, California continental borderland. 201 records from Assemblage of living benthic foraminifera in sediment core GeoB3708-1. 142 records from Assemblage of living benthic foraminifera in sediment core GeoB4904-7. 144 records from Benthic foraminiferal assemblage (dead) in MUC OB10-K, size fraction 63-150 µm. 112 records from Benthic foraminiferal assemblage (dead) in MUC SC2-L, size fraction 63-150 µm. 1100 records from (Fig. 6) Assemblage of benthic foraminifera in sediment core GeoB6730-1. 36 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, >125 µm fraction. 13 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, 30-63 µm fraction. 25 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, 63-125 µm fraction. 17 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, >125 µm fraction. 19 records from Assemblage of living benthic foraminifera in sediment core CD145_55803#5, >150 µm. 69 records from (Table T6) Calcareous nannofossil stratigraphy of ODP Hole 198-1210A. 43 records from Assemblage of living benthic foraminifera in sediment core CD145_55808#3, 63-150 µm. 140 records from Assemblage of living benthic foraminifera in sediment core GeoB1720-3. 120 records from Assemblage of living benthic foraminifera in sediment core GeoB3604-1. 207 records from Assemblage of living benthic foraminifera in sediment core GeoB3711-1. 162 records from Assemblage of living benthic foraminifera in sediment core GeoB4916-4. 588 records from (Table 5) Foraminiferal numbers of empty test of important species in surface sediments. 75 records from Faunal assemblage of sediment core GS7603-9. 79 records from Total foraminifera counts from M35/1_MSN1055. 21 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, >150 µm. 26 records from Assemblage of living benthic foraminifera in sediment core CD146_55901#11, >150 µm. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55916#1, >150 µm. 17 records from Assemblage of living benthic foraminifera in sediment core CD146_55918#7, >150 µm. 13737 records from Scottish Borders Biological Records Centre - SWT Scottish Borders Local Wildlife Site Survey data 1996-2000 - species information. 21 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, >150 µm. 27 records from Assemblage of living benthic foraminifera in sediment core CD145_55803#5, 63-150 µm. 19 records from Assemblage of living benthic foraminifera in sediment core CD145_55818#4, 63-150 µm. 30 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, 63-150 µm. 66 records from Assemblage of living benthic foraminifera in sediment core CD146_55901#11, 63-150 µm. 23 records from Assemblage of living benthic foraminifera in sediment core CD146_55918#7, 63-150 µm. 569 records from LUSC - Herbário de Lages da Universidade do Estado de Santa Catarina. 248 records from Counts of Quaternary foraminifera of sediment core CRP-1 (App. 1). 119 records from Assemblage of living benthic foraminifera in sediment core GeoB4915-3. 516 records from (Appendix B1) Calcareous nannofossils of ODP Site 208-1262. 109 records from Assemblage of living benthic foraminifera in sediment core GeoB3703-4. 129 records from Assemblage of living benthic foraminifera in sediment core GeoB3705-2. 190 records from Assemblage of living benthic foraminifera in sediment core GeoB3706-3. 220 records from Assemblage of living benthic foraminifera in sediment core GeoB4917-5. 89 records from Assemblage of living benthic foraminifera in sediment core GeoB4918-4. 347 records from (Table 4) Standing stock values of important species in surface sediments. 73 records from Faunal assemblage of sediment core GS7603-13. 891 records from Benthic foraminifera accumulation rate of sediment core MD01-2378 during marine isotope stage 3. 181 records from Occurence of monothalamous foraminifera in Admiralty Bay, King George Island, West Antarctica (Table 1, 2). 359 records from (Appendix A) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene desiments of DSDP Hole 94-607 from the North Atlantic. 671 records from (Appendix B) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene sediments of DSDP Hole 94-610A from the North Atlantic. 1070 records from (Table 1) Distribution of agglutinated benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 66 records from (Table 2) Distribution of calcareous benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 1666 records from Occurrence of planktic foraminifera in Pliocene to Holocene sediments of DSDP Hole 81-552A in the North Atlantic (Appendix 2). 76 records from Faunal assemblage of sediment core GS7603-10. 77 records from Faunal assemblage of sediment core GS7603-12. 76 records from Faunal assemblage of sediment core GS7603-8. 87 records from Stable isotopes measured on Ammonia beccarii from sediment core GIK12523-1. 442 records from Distribution of planktic foraminifera of sediment trap NB7. 587 records from (Table 2) Raw counts of planktonic foraminiferal species and varieties from the sediment surface samples from the South China Sea. 10183 records from Planktic foraminifera counts of sediment core MD95-2040. 165 records from Total foraminifera counts from multinet M31/3_MSN898. 10465 records from Plecoptera of Ireland. 235 records from Total foraminifera counts from multinet M31/3_MSN905. 181 records from Total foraminifera counts from multinet M31/3_MSN914. 228 records from Total foraminifera counts from multinet M31/3_MSN917. 1028 records from Anfibios y Reptiles reportados en humedales del departamento de Córdoba. 128 records from Total foraminifera counts of multinet M33/1_MSN1030. 163 records from Total foraminifera counts from multinet SO119_MSN1285. 10 records from Plasm bearing foraminifera counts from multinet M31/2_MSN891. 18 records from Plasm bearing foraminifera counts from multinet M31/2_MSN897. 23 records from Plasm bearing foraminifera counts from multinet M32/3_MSN958. 152 records from Plasm bearing foraminifera counts of multinet SO118_MSN1252. 70 records from Plasm bearing foraminifera counts from multinet SO119_MSN1283. 45 records from Plasm bearing foraminifera counts from multinet SO119_MSN1286. 84 records from Total foraminifera counts from M35/1_MSN1051. 6883 records from Kingfisher Survey 2010. 52 records from Total foraminifera counts from M35/1_MSN1058. 45 records from Wasser-Lernort Nettemündung. 148 records from Faunal assemblage of sediment core GS7603-11. 70 records from Faunal assemblage of sediment core GS7603-14. 1023 records from (Appendix Table 1) Number of planktonic foraminiferal genera and species in Late Creatceous sediments of ODP Hole 122-762C from the Exmouth Plateau, eastern Indian Ocean. 2381 records from Hawaiian Algal Database. 269 records from Distribution of planktic foraminifera of sediment trap NB6. 232 records from Distribution of planktic foraminifera of sediment trap OG5. 119 records from Total foraminifera counts from multinet M31/2_MSN892. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 238 records from Total foraminifera counts from multinet M31/3_MSN913. 174 records from Total foraminifera counts from multinet M31/3_MSN915. 215 records from Total foraminifera counts from multinet M31/3_MSN921. 324 records from Total foraminifera counts from multinet M32/5_MSN974. 112 records from Total foraminifera counts of multinet M33/1_MSN1029. 88 records from Total foraminifera counts of multinet SO118_MSN1265. 172 records from Total foraminifera counts of multinet SO118_MSN1266. 124 records from Total foraminifera counts of multinet SO118_MSN1267. 189 records from Total foraminifera counts from multinet SO119_MSN1282. 186 records from Total foraminifera counts from multinet SO119_MSN1283. 161 records from Total foraminifera counts from multinet SO119_MSN1286. 5 records from Plasm bearing foraminifera counts from multinet M31/2_MSN887. 12 records from Plasm bearing foraminifera counts from multinet M31/2_MSN892. 10 records from Plasm bearing foraminifera counts from multinet M31/2_MSN894. 11 records from Plasm bearing foraminifera counts from multinet M31/2_MSN896. 91 records from Plasm bearing foraminifera counts from multinet M32/3_MSN957. 51 records from Plasm bearing foraminifera counts from multinet SO119_MSN1285. 233 records from Total foraminifera counts from M35/1_MSN1044. 62 records from Total foraminifera counts from M35/1_MSN1054. 75 records from Faunal assemblage of sediment core TR149-32. 72 records from Faunal assemblage of sediment core TR149-35. 76 records from Faunal assemblage of sediment core TR149-37. 1100 records from (Table AT3) Planktonic foraminiferal stratigraphy of ODP Hole 182-1128B. 676 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 94-608 in the North Atlantic. 239 records from Planktic foraminifera counts at CTD station M39/4_352CTD-11. 149 records from Total foraminifera counts from multinet M31/2_MSN888. 146 records from Total foraminifera counts from multinet M31/2_MSN891. 95 records from Total foraminifera counts from multinet M31/2_MSN896. 91 records from Total foraminifera counts from multinet M31/2_MSN897. 202 records from Total foraminifera counts from multinet M31/3_MSN900. 165 records from Total foraminifera counts from multinet M31/3_MSN903. 179 records from Total foraminifera counts from multinet M31/3_MSN906. 222 records from Total foraminifera counts from multinet M31/3_MSN910. 195 records from Total foraminifera counts from multinet M31/3_MSN923. 228 records from Total foraminifera counts from multinet M32/5_MSN975. 149 records from Total foraminifera counts of multinet SO117_MSN1243. 159 records from Total foraminifera counts of multinet SO118_MSN1251. 89 records from Total foraminifera counts from multinet SO119_MSN1303. 19 records from Plasm bearing foraminifera counts from multinet M31/2_MSN888. 114 records from Plasm bearing foraminifera counts of multinet SO117_MSN1243. 117 records from Plasm bearing foraminifera counts of multinet SO117_MSN1244. 83 records from Total foraminifera counts from M35/1_MSN1043. 97 records from Total foraminifera counts from M35/1_MSN1048. 6 records from Wuhle - Brücke / B1. 915 records from (Appendix Table 2) Number of planktonic foraminiferal genera and species in Late Creatceous sediments of ODP Hole 122-763B from the Exmouth Plateau, eastern Indian Ocean. 2464 records from Benthic foraminiferal abundances at the Cretaceous/Paleogene boundary of ODP Hole 117-1049C at Blake Nose, Northwest Atlantic (Appendix A). 36 records from Stable isotopes measured on Ammonia beccarii from sediment core GIK12594-2. 6278 records from TestWat - Macroinvertebrates and macrophytes of freshwater bodies in Flanders, Belgium. 147 records from Total foraminifera counts from multinet M31/2_MSN889. 113 records from Total foraminifera counts from multinet M31/2_MSN890. 121 records from Total foraminifera counts from multinet M31/2_MSN893. 96 records from Total foraminifera counts from multinet M31/2_MSN894. 128 records from Total foraminifera counts from multinet M31/2_MSN895. 206 records from Total foraminifera counts from multinet M31/3_MSN907. 227 records from Total foraminifera counts from multinet M31/3_MSN916. 227 records from Total foraminifera counts from multinet M31/3_MSN918. 131 records from Total foraminifera counts from multinet M32/3_MSN956. 145 records from Total foraminifera counts from multinet M32/3_MSN957. 38865 records from Countryside Council for Wales - 1996 - 2005 CCW Marine Intertidal Phase 1 species dataset. 194 records from Total foraminifera counts from multinet M32/3_MSN958. 233 records from Total foraminifera counts from multinet M32/5_MSN976. 115 records from Total foraminifera counts of multinet M33/1_MSN1028. 436 records from Total foraminifera counts of multinet SO118_MSN1252. 205 records from Total foraminifera counts from multinet SO119_MSN1281. 134 records from Total foraminifera counts from multinet SO119_MSN1284. 18 records from Plasm bearing foraminifera counts from multinet M31/2_MSN889. 9 records from Plasm bearing foraminifera counts from multinet M31/2_MSN890. 12 records from Plasm bearing foraminifera counts from multinet M31/2_MSN895. 68 records from Plasm bearing foraminifera counts from multinet M32/3_MSN956. 361 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 90-590B in the southwestern Pacific. 124 records from Stable isotope data and sedimentology of core SO42-74KL. 29 records from Abundance of Globorotalia menardii of sediment core GeoB2821-1. 22 records from Abundance of Globorotalia menardii of sediment core GeoB2822-2. 14 records from Abundance of Globorotalia menardii of sediment core GeoB2110-3. 234 records from Size of planktic foraminifera at CTD station M39/4_352CTD-11. 131 records from Total foraminifera counts from multinet M31/2_MSN887. 206 records from Total foraminifera counts from multinet M31/3_MSN908. 184 records from Total foraminifera counts of multinet SO117_MSN1244. 229 records from Total foraminifera counts of multinet SO117_MSN1245. 220 records from Total foraminifera counts of multinet SO118_MSN1253. 148 records from Total foraminifera counts from multinet SO119_MSN1278. 92 records from Total foraminifera counts from multinet SO119_MSN1295. 14 records from Plasm bearing foraminifera counts from multinet M31/2_MSN893. 43 records from Total foraminifera counts from M35/1_MSN1045. 134 records from Total foraminifera counts from M35/1_MSN1046. 198 records from Total foraminifera counts from M35/1_MSN1047. 250 records from Mosquitoes (Diptera: Culicidae) of Ireland. 33 records from Total foraminifera counts from M35/1_MSN1053. 98 records from Total foraminifera counts from M35/1_MSN1067. 87 records from Plasm bearing foraminifera counts from M35/1_MSN1049. 84 records from Plasm bearing foraminifera counts from M35/1_MSN1056. 33 records from Marine Conservation Society - Palinurus elephas or Crawfish sightings in the UK and Ireland from 1969 to the present time.. 95 records from Nematode densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC09. 63 records from Plasm bearing foraminifera counts of multinet SO118_MSN1253. 55 records from Plasm bearing foraminifera counts of multinet SO118_MSN1265. 63 records from Plasm bearing foraminifera counts of multinet SO118_MSN1266. 50 records from Plasm bearing foraminifera counts of multinet SO118_MSN1267. 138 records from Plasm bearing foraminifera counts from multinet SO119_MSN1278. 180 records from Plasm bearing foraminifera counts from multinet SO119_MSN1281. 141 records from Plasm bearing foraminifera counts from multinet SO119_MSN1282. 94 records from Plasm bearing foraminifera counts from multinet SO119_MSN1284. 91 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 77 records from Plasm bearing foraminifera counts from multinet SO119_MSN1303. 79 records from Total foraminifera counts from M35/1_MSN1049. 126 records from Total foraminifera counts from M35/1_MSN1050. 49 records from Total foraminifera counts from M35/1_MSN1052. 54 records from Total foraminifera counts from M35/1_MSN1057. 210 records from RSPB - Black grouse lek survey in the Scottish Borders, 2010 (Southern Upland Partnership). 60 records from Total foraminifera counts from M35/1_MSN1063. 125 records from Plasm bearing foraminifera counts from M35/1_MSN1043. 94 records from Plasm bearing foraminifera counts from M35/1_MSN1044. 87 records from Plasm bearing foraminifera counts from M35/1_MSN1045. 149 records from Plasm bearing foraminifera counts from M35/1_MSN1046. 50 records from Plasm bearing foraminifera counts from M35/1_MSN1047. 208 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (forofitos). 5 records from Plasm bearing foraminifera counts from M35/1_MSN1055. 53 records from Plasm bearing foraminifera counts from M35/1_MSN1058. 113 records from Plasm bearing foraminifera counts from M35/1_MSN1062. 108 records from Plasm bearing foraminifera counts from M35/1_MSN1065. 66 records from Total foraminifera counts from M35/1_MSN1059. 108 records from Total foraminifera counts from M35/1_MSN1070. 77 records from Total foraminifera counts from M35/1_MSN1075. 120 records from Plasm bearing foraminifera counts from M35/1_MSN1060. 196 records from Plasm bearing foraminifera counts from M35/1_MSN1067. 90 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 1734 records from Aves Marinas y Playeras en el PNN Sanquianga y la Bocana de Iscuandé entre 2007 y 2009. 61 records from Total foraminifera counts of multinet M10/2_MSN229. 156 records from Total foraminifera counts of multinet M10/2_MSN261. 49 records from Total foraminifera counts of multinet M10/2_MSN284. 135 records from Total foraminifera counts of multinet M11/1_MSN522. 82 records from Total foraminifera counts of multinet FCA97C_MSN1346. 126 records from Total foraminifera counts of multinet M12/3_MSN558. 58 records from Plasm bearing foraminifera counts of multinet M12/3_MSN560. 137 records from Total foraminifera counts of multinet M21/3_MSN661. 62 records from Total foraminifera counts of multinet M21/4_MSN700. 51 records from Total foraminifera counts of multinet M21/4_MSN712. 41 records from Total foraminifera counts of multinet M21/4_MSN714. 57 records from Total foraminifera counts of multinet M21/4_MSN718. 56 records from Total foraminifera counts of multinet M21/4_MSN720. 34 records from Total foraminifera counts of multinet M21/4_MSN722. 211 records from Total foraminifera counts of multinet M21/1_MSN610. 118 records from Total foraminifera counts from M35/1_MSN1060. 5550 records from Biodiversity records from Ireland - general. 157 records from Total foraminifera counts from M35/1_MSN1069. 94 records from Total foraminifera counts from M35/1_MSN1074. 169 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 67 records from Plasm bearing foraminifera counts from M35/1_MSN1054. 40 records from Plasm bearing foraminifera counts from M35/1_MSN1057. 64 records from Plasm bearing foraminifera counts from M35/1_MSN1063. 160 records from Plasm bearing foraminifera counts from M35/1_MSN1068. 26360 records from Diveboard - Scuba diving citizen science observations. 124 records from Total foraminifera counts of multinet M10/2_MSN232. 49 records from Total foraminifera counts of multinet M10/2_MSN251. 132 records from Total foraminifera counts of multinet M10/2_MSN315. 120 records from Total foraminifera counts of multinet M10/2_MSN319. 108 records from Total foraminifera counts of multinet M11/1_MSN524. 150 records from Total foraminifera counts of multinet M12/3_MSN533. 124 records from Total foraminifera counts of multinet M12/3_MSN559. 299 records from Total foraminifera counts of multinet M21/3_MSN662. 135 records from Total foraminifera counts of multinet M21/3_MSN688. 76 records from Total foraminifera counts of multinet M21/4_MSN724. 51 records from Total foraminifera counts of multinet M27/2_MSN884. 238 records from Coccoliths in ODP Hole 104-643A. 97 records from Total foraminifera counts from M35/1_MSN1061. 80 records from Total foraminifera counts from M35/1_MSN1062. 66 records from Total foraminifera counts from M35/1_MSN1064.
Keywords: GBIF; biodiversity; species occurrences